Curable composition containing water-insoluble polyfunctional (meth) acrylamide
A curable composition with water-insoluble polyfunctional (meth)acrylamide and a polymerizable compound addresses issues of curability, transparency, and adhesion, providing versatile applications in both aqueous and organic systems.
Patent Information
- Application Number
- CN202380041134.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-30
- Filing Date
- 2023-03-28
- Publication Date
- 2024-12-31
AI Technical Summary
Existing curable compositions face challenges in achieving high curability, transparency, and adhesion to various substrates while being usable in both aqueous and organic systems, with issues related to viscosity, operability, and curing shrinkage.
A curable composition containing a water-insoluble polyfunctional (meth)acrylamide and a polymerizable compound, which allows for high wettability, adhesion, and solubility in both water and organic solvents, enabling UV and thermal curing, and adjustable viscosity.
The composition exhibits high curability, transparency, and adhesion to diverse substrates, with good operability and solubility, suitable for applications such as inks, coatings, adhesives, and dental materials, and can be used in both aqueous and organic systems.
Smart Images

Figure BDA0005138945970000051 
Figure BDA0005138945970000052 
Figure BDA0005138945970000061
Abstract
Description
Technical Field
[0001] The present disclosure relates to a curable composition containing a water-insoluble polyfunctional (meth)acrylamide. Background Art
[0002] An N-substituted or N,N-disubstituted (meth)acrylamide having two or more (meth)acrylamide groups in the molecule is called a polyfunctional (meth)acrylamide and is widely used as a formulation component of an ultraviolet (UV; Ultraviolet) or thermosetting resin. Polyfunctional (meth)acrylamides have various structures depending on the type and number of their substituents, and can widely cover physical properties or functions such as from liquid to solid, from hydrophilic (high polarity) to hydrophobic (low polarity), and from low viscosity to high viscosity. Therefore, they are used in extremely many fields such as inks, adhesives (Japanese: 粘着剤), binders (Japanese: 接着剤), various coating agents or paints, nail cosmetics or dental materials, cosmetics or medical materials such as contact lenses, reactive diluents for ultraviolet (UV) curable resins, and crosslinking agents for thermal polymerization or photopolymerization.
[0003] In recent years, as one of the causes of air pollution, volatile organic compounds (VOCs; Volatile Organic Compounds) have been regarded as a problem, and it has been required to suppress the emission amount of VOCs in various fields. Therefore, water-based (aqueous) curable compositions that do not contain organic solvents or the like and use water as a solvent, or active energy ray curable compositions such as UV or EB (Electron Beam) that do not contain organic solvents and water have received attention. In particular, a water-based curable composition that uses water as a solvent requires a very large amount of energy to dry the water. In contrast, active energy ray curable compositions are highly expected because of their energy saving and low environmental load. Furthermore, a water-soluble or water-dispersible aqueous UV curable resin undergoes a polymerization reaction (curing) by irradiation with active energy rays, and then, the heat generated is used to evaporate the water. By simultaneously performing UV curing and drying, a cured film can be rapidly obtained even with a small amount of energy. By adjusting the water content, the viscosity of the composition can be adjusted or shrinkage during curing (curing shrinkage) can be suppressed. Therefore, research on the above compositions is being actively carried out. Summary of the Invention
[0004] Technical Problem to be Solved by the Invention
[0005] The present invention discloses a curable composition having high curability and transparency, and having good wettability and adhesion to various substrates, being liquid at room temperature, having excellent operability, being usable in both aqueous and organic systems, and being suitable for UV curing and / or thermal curing. In addition, a coating composition, an adhesive composition, an adhesive composition, an ink composition, an aqueous ink composition, an ink composition for three-dimensional modeling, an aqueous coating composition, a sealant composition, a nail cosmetic composition, a dental material composition, a decorative coating composition, and their cured products and molded products are provided.
[0006] Technical means for solving technical problems
[0007] The inventors have found that the above-mentioned technical problems can be solved by using a curable composition containing a water-insoluble polyfunctional (meth)acrylamide (A) and a polymerizable compound (B) other than (A).
[0008] Effects of the Invention
[0009] The curable composition disclosed herein contains a water-insoluble multifunctional (meth)acrylamide (A) and a polymerizable compound (B), and has high curability. Through the interaction between A and B, the curable composition has high wettability and adhesion to various substrates from low-polarity resin materials to high-polarity glass or metal materials, has good mutual solubility with water and organic solvents from low polarity to high polarity or a variety of general-purpose monomers, and has high transparency. The curable composition is liquid at room temperature, has good operability, and the viscosity of the curable composition can be adjusted from low viscosity to high viscosity without restriction according to the application. The curable composition disclosed herein can be used in both aqueous and organic systems, and can also be used for UV curing and / or thermal curing, and can thus be preferably used in various applications such as inkjet printing, screen printing, lithography, flexographic printing, gravure printing, and other printing ink compositions, three-dimensional modeling ink compositions, coating compositions, adhesive compositions, adhesive compositions, coating compositions, sealant compositions, nail cosmetics, decorative coating agents used in decorative films or decorative sheets, and dental materials. DETAILED DESCRIPTION
[0010] The following describes the embodiments of the present disclosure in detail, but the scope of the present invention is not limited to the embodiments described herein, and various changes can be made within the scope of the gist of the present invention. In addition, when a plurality of upper limits and lower limits are recorded for a specific parameter, any upper limit and lower limit of the upper limit and lower limit can be combined to set a preferred numerical range.
[0011] One embodiment of the present disclosure is a curable composition (D) containing a multifunctional (meth)acrylamide (A) and a polymerizable compound (B). Multifunctional (meth)acrylamide (A) is a compound having two or more (meth)acrylamide groups in the molecule. The number of (meth)acrylamide groups in A is preferably six or less. If the number of (meth)acrylamide groups exceeds six, the acrylic acid equivalent becomes smaller, the shrinkage of the curable composition during curing becomes larger, and the obtained cured film becomes prone to deformation or cracking. In addition, the viscosity and polarity of A are increased by hydrogen bonds formed between the (meth)acrylamide groups, and the handling of A or the mutual solubility of A and the above-mentioned B may deteriorate. From the same point of view, the number of (meth)acrylamide groups in A is more preferably 4 or less.
[0012] Although the multifunctional (meth) acrylamide (A) is water-insoluble alone, it is an amphiphilic compound. A becomes soluble in water by coexisting with a water-soluble polymerizable compound (B), and becomes soluble in a low-polarity organic solvent by coexisting with a water-insoluble polymerizable compound (B). Therefore, the curable composition (D) containing A and B can be used in both aqueous and organic systems. By adjusting the types and contents of A and B, it has good mutual solubility with water and organic solvents from low polarity to high polarity or a variety of general-purpose monomers, and has high transparency. In addition, when used as an aqueous curable composition such as an aqueous ink or an aqueous coating, the drying and curing properties are both good, and the ink film (image) or the coating film after evaporation of water does not produce unevenness or turbidity of the image, and the effect of maintaining transparency, smoothness, and glossiness is exerted. Furthermore, since the polyfunctional (meth)acrylamide (A) has one or more (meth)acrylamide groups in the molecule and the polymerizable compound (B) has one or more polymerizable groups in the molecule, the curable composition (D) containing A and B has high curability by active energy rays such as ultraviolet rays (UV) and electron beams (EB) and / or heat, and the obtained cured product is also excellent in strength, hardness, heat resistance, etc.
[0013] One embodiment of the present disclosure is that the solubility parameter (SP value) of the multifunctional (meth)acrylamide (A) is 8.8 (cal / cm 3 ) 1 / 2 To 11.0 (cal / cm 3 ) 1 / 2 The curable composition (D) containing A and a polymerizable compound (B) (except (A)). The dissolved SP value in the present disclosure is calculated by the Fedors method described in Polymer Engineering Science, Vol. 14, P. 147, Y. 1974, and the unit is (cal / cm 3 ) 1 / 2. The higher the SP value, the higher the hydrophilicity of the compound, and the lower the SP value, the higher the hydrophobicity of the compound. The SP value of the multifunctional (meth)acrylamide (A) is in the range of 8.8 to 11.0 (units omitted below), and A has amphiphilic properties that exhibit both hydrophilicity and hydrophobicity. Due to the amphiphilicity of (meth)acrylamide (A) and the high cohesion and high adhesion to the substrate derived from the (meth)acrylamide group, the curable composition (D) has high wettability, adhesion, and adhesion to various substrates ranging from low-polarity resin materials to high-polarity glass or metal materials. Coating compositions, adhesive compositions, ink compositions, etc. containing the curable composition (D) have high wettability, adhesion, and adhesion. In addition, the adhesive composition containing D has high adhesion.
[0014] One embodiment of the present disclosure is the above-mentioned curable composition (D) in which the SP value of the polymerizable compound (B) (excluding the multifunctional (meth) acrylamide (A)) is 8.5 to 14.5. The SP value of the polymerizable compound (B) is within this range, and B has hydrophilicity, hydrophobicity, or amphiphilicity of hydrophilicity and hydrophobicity depending on the type. Therefore, the polymerizable compound (B) and the multifunctional (meth) acrylamide (A) have good mutual solubility, the curable composition (D) containing A and B has high transparency, and the transparency of the cured product obtained by curing D is also high. In addition, the curable composition (D) has good solubility in water or various organic solvents, and can be preferably used in both aqueous and organic systems. In the present disclosure, the water system and water in the water-based curable composition, the water-based ink composition, or the water-based coating composition refer to the water in the total mass of the volatile components in various compositions accounting for more than 60% by mass. Similarly, the organic system and organicity in the organic curable composition, the organic ink composition, or the organic coating composition refer to the organic components in the total mass of the volatile components in various compositions accounting for more than 60% by mass. In addition, when it is not recorded as water-based or water-based below, it refers to organic or organic. The above-mentioned various compositions containing such curable composition (D) can be obtained regardless of whether it is organic or water-based, especially in water-based ink composition and water-based coating composition, the pigment dispersibility of curable composition (D) is good, and the printing characteristics of the ink composition such as discharge stability and printing clarity, surface smoothness, surface gloss, etc. make the coating composition cured and the surface characteristics of the coating obtained are excellent.
[0015] One embodiment of the present disclosure is the above-mentioned various curable compositions (D) in which the absolute value of the difference between the SP values of multifunctional (meth) acrylamide (A) and polymerizable compound (B) is less than 3.0. Since the closer the SP values of A and B are, the closer the hydrophilicity or hydrophobicity of A and B is, the more mutually soluble A and B are, and the transparency of the cured product of curable composition (D) and D is excellent. From this point of view, the absolute value of the difference between the SP values of A and B is preferably less than 2.5, more preferably less than 1.5. The colorless, transparent transparent coating composition, adhesive composition, adhesive composition, ink composition, three-dimensional shaping ink composition, coating composition, sealing material composition, nail cosmetics, dental materials, decorative coating agents and the colorless, transparent cured products and molded products of such materials containing curable composition (D) can be obtained, which can be preferably used as materials for optical components or electronic devices. In addition, when the curable composition uses two or more polyfunctional (meth)acrylamides (A) and / or polymerizable compounds (B), the SP value of A is a value obtained by weighted average based on the weight ratio of all A, and the SP value of B is a value obtained by weighted average based on the weight ratio of all B. In addition, when A or B has a repeating unit in the structure, the SP values of A and B are weighted average values.
[0016] One embodiment of the present disclosure is the various curable compositions (D) described above, wherein the acrylic acid equivalent of the multifunctional (meth)acrylamide (A) is 180 or more. The acrylic acid equivalent in the present disclosure is the molecular weight equivalent to each (meth)acrylamide group, that is, the value obtained by dividing the molecular weight by the number of acryloyl groups. If the acrylic acid equivalent is low, the density of the (meth)acrylamide group is high, the curability is high, but the resistance to curing shrinkage is low. If the acrylic acid equivalent of the multifunctional (meth)acrylamide (A) is less than 180, the density of the (meth)acrylamide group as a hydrophilic functional group in the A molecule is too high, and A may become solid or water-soluble at room temperature, which may be difficult to operate or the obtained curable composition or cured product may become turbid or uneven. In addition, the normal temperature in the present disclosure refers to the temperature range of 5°C to 35°C. The higher the acrylic acid equivalent of the multifunctional (meth)acrylamide (A), the easier it is to achieve a balance between hydrophilicity and hydrophobicity, so it is preferred. However, if it exceeds 3000, the molecular weight and viscosity of A may increase, and the workability and curability may deteriorate. From these viewpoints, the acrylic acid equivalent of A is preferably 190 to 2500, and more preferably 200 to 2000.
[0017] One embodiment of the present disclosure is the above-mentioned various curable compositions (D) in which the polyfunctional (meth)acrylamide (A) is a compound represented by the general formula [1] to the general formula [4].
[0018] [Chemical formula 1]
[0019]
[0020] [Chemical formula 2]
[0021]
[0022] [Chemical formula 3]
[0023]
[0024] [Chemical formula 4]
[0025]
[0026] In the general formulas [1] to [4], R 1 represents a hydrogen atom or a methyl group. 2 and R 3 All represent a divalent chain hydrocarbon group having 3 carbon atoms, and may be a linear or branched structure, and may be the same or different. 4 represents a hydrogen atom or a chain hydrocarbon group having 1 to 2 carbon atoms. n is an integer from 1 to 70, and m is 0 or 1. x1 and z1 are each independently an integer from 1 to 10, y1 is an integer from 1 to 40, x2, y2 and z2 are each independently an integer from 1 to 30, and s3, x3, y3 and z3 are each independently an integer from 1 to 20.
[0027] The polyfunctional (meth)acrylamide (A) represented by general formula [1] to general formula [4] specifically includes: polypropylene di(meth)acrylamide, polypropylene polyethylene di(meth)acrylamide, trimethylolpropane polypropylene tri(meth)acrylamide, pentaerythritol polypropylene tetra(meth)acrylamide, etc. When the number of repeating units of propylene oxide and ethylene oxide in these compounds is 1 to 30, it is easy to adjust the balance between the acrylic acid equivalent and viscosity of A. That is, it is preferred to have an appropriate acrylic acid equivalent, be liquid or waxy at room temperature, and have good operability. From these viewpoints, the number of repeating units is more preferably 1 to 20, and particularly preferably 2 to 10.
[0028] In the case where the multifunctional (meth)acrylamide (A) is a compound having a structure shown in general formula [1] to general formula [4], it has multiple ether groups in the molecule, which has the effect of preventing the hindrance of photo-radical polymerization caused by oxygen, and is therefore preferred. In addition, by having a repeating unit with an isopropyloxy group, A is hydrophilic, and the cured product of the curable composition containing A can obtain a sufficiently satisfactory water resistance. In addition, although the multifunctional (meth)acrylamide (A) shown in general formula [1] to general formula [4] is non-water-soluble, a water-soluble or water-dispersible aqueous curable composition can be prepared by combining (A) with a water-soluble curable compound (B). This is because (A) contains multiple hydrophilic (meth)acrylamide groups and is therefore easily miscible with the water-soluble B at a molecular level. Furthermore, the polyfunctional (meth)acrylamide (A) of the general formula [3] and the general formula [4] is trifunctional or tetrafunctional, but has a branched structure, and thus has the characteristic of low shrinkage accompanying curing, similar to the bifunctional (A) of the general formula [1] and the general formula [2].
[0029] One embodiment of the present disclosure is a curable composition (D) in which the content of multifunctional (meth) acrylamide (A) is 1% to 95% by mass and the content of polymerizable compound (B) is 5% to 99% by mass relative to the total mass of the curable composition. If the contents of A and B are within these ranges, the obtained curable composition can satisfy all the physical properties and characteristics such as low viscosity, low curing shrinkage, high transparency, high curability, high wettability and adhesion, and can be dissolved or dispersed in organic solvents and water, and can obtain various forms of curable compositions (D) such as organic, aqueous, and emulsions. Although multifunctional (meth) acrylamide (A) is non-water-soluble, it becomes soluble in water by coexisting with a water-soluble polymerizable compound (B), so that a water-based curable composition can be easily obtained. In the present disclosure, soluble in water (water-soluble) means that more than 1g is dissolved in 100g of water at 25°C to obtain a stable aqueous solution. In addition, from the viewpoint that the strength, hardness, heat resistance, etc. of the cured product obtained by curing the curable composition (D) can be easily adjusted according to various uses, the contents of A and B in D are preferably 2 mass % to 90 mass % and 10 mass % to 98 mass %, respectively, and more preferably 5 mass % to 80 mass % and 20 mass % to 95 mass %, respectively.
[0030] One embodiment of the present disclosure is the above-mentioned various curable compositions (D) in which the polymerizable compound (B) has one or more polymerizable groups selected from the group consisting of (meth)acrylate, (meth)acrylamide, vinyl, vinyl ether, methyl vinyl ether, allyl, (meth)allyl ether, maleimide, α-substituted maleimide, and α, β-substituted maleimide in the molecule. In addition, B is a compound other than multifunctional (meth)acrylamide (A). The polymerizable group of the polymerizable compound (B) has an ethylenically unsaturated bond, which can be polymerized by energy such as light or heat, and a cross-linked polymer (cured material) can be obtained by polymerization reaction with multifunctional (meth)acrylamide (A). From the viewpoint of high polymerizability, the polymerizable group of B is preferably (meth)acrylate, (meth)acrylamide and vinyl. From the viewpoint of having a self-photopolymerization initiation effect by irradiation with active energy rays such as light, vinyl ether groups, methyl vinyl ether groups, (methyl) allyl ether groups, maleimide groups, α-substituted maleimide groups, and α, β-substituted maleimide groups are preferred. The selection of the polymerizable group of the polymerizable compound (B) can be adjusted and designed according to the preferred physical properties or characteristics of the curable composition (D) and the cured product obtained by curing D.
[0031] One embodiment of the present disclosure is that the polymerizable compound (B) contains the above-mentioned various curable compositions (D) of monofunctional polymerizable compounds (b1) and / or polyfunctional polymerizable compounds (b2). Relative to the total mass of the curable composition, the content of (b1) is 0% to 80% by mass, and the content of (b2) is 0% to 40% by mass. By containing b1 or b2, it is possible to obtain a curable composition containing polyfunctional (meth) acrylamide (A) and polymerizable compounds (B), high curability and transparency, and good wettability and adhesion to various substrates. In addition, by containing b1 and b2, it is possible to obtain a curable composition that is liquid at room temperature, has excellent operability, and is available in both aqueous and organic systems. From the viewpoint that monofunctional polymerizable compounds (b1) reduce the viscosity of curable compositions (D) and can improve operability, the content of b1 is preferably 5% by mass or more, more preferably 10% by mass or more, and particularly preferably 20% by mass or more. On the other hand, if the content of b1 exceeds 80% by mass, the total of the multifunctional (meth) acrylamide (A) and the multifunctional polymerizable compound (b2) in the curable composition (D) is less than 20% by mass, and depending on the purpose of D, the surface hardness and strength of the obtained cured product are sometimes not fully satisfactory. From the viewpoint that the multifunctional polymerizable compound (b2) can improve the curability of the curable composition (D), the content of b2 is preferably 2% by mass or more, more preferably 5% by mass or more, and particularly preferably 10% by mass or more. On the other hand, if the content of b2 exceeds 40% by mass, the total of the multifunctional (meth) acrylamide (A) and the multifunctional polymerizable compound (b2) in the curable composition (D) exceeds 41% by mass, and the curing shrinkage of D becomes high, and the obtained cured product is likely to produce deformation or cracks.
[0032] The monofunctional polymerizable compound (b1) and the polyfunctional polymerizable compound (b2) have one or more polymerizable groups arbitrarily selected from the group of the above-mentioned various polymerizable groups. In addition, from the viewpoint of high polymerizability, curability and hydrophilicity, the polymerizable groups of b1 and b2 are preferably (meth)acrylate groups and (meth)acrylamide groups. Furthermore, in the water-based curable composition, it is particularly preferred to use water-soluble b1 and / or b2.
[0033] As for the monofunctional polymerizable compound (b1), examples of the monofunctional (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, hydroxyethyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, tridecyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, propoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, methoxydiethylene glycol (meth)acrylate, methoxytriethylene glycol (meth)acrylate, methoxytetraethylene glycol (meth)acrylate, and (meth)acrylic acid. acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxytetraethylene glycol (meth)acrylate, phenoxyhexaethylene glycol (meth)acrylate, methoxydipropylene glycol (meth)acrylate, methoxytripropylene glycol (meth)acrylate, cyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, bornyl (meth)acrylate, isobornyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, allyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxyhexyl (meth)acrylate, and the like.
[0034] As for the monofunctional polymerizable compound (b1), examples of the monofunctional (meth)acrylamide include: N-alkyl (saturated or unsaturated straight chain or branched chain structure of 1 to 18 carbon atoms) (meth)acrylamide such as N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-propyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-butyl (meth)acrylamide, N-isobutyl (meth)acrylamide, and N-hexyl (meth)acrylamide; N-alkoxy (straight chain or branched chain structure of 1 to 6 carbon atoms) alkyl (straight chain or branched chain structure of 1 to 6 carbon atoms) (meth)acrylamide; N-methoxymethyl (meth)acrylamide, N-ethoxymethyl (meth)acrylamide, N-methoxyethyl (meth)acrylamide, N-ethoxyethyl (meth)acrylamide, and N-n-butoxymethyl (meth)acrylamide; Alkyl (straight or branched chain structure of 1 to 6 carbon atoms) (meth) acrylamide; hydroxyalkyl (straight or branched chain structure of 1 to 6 carbon atoms) (meth) acrylamide such as N-isobutoxymethyl (meth) acrylamide, N-vinyl pyrrolidone, N-vinyl caprolactam, N-(2-hydroxyethyl) (meth) acrylamide, N-(2-hydroxypropyl) (meth) acrylamide, and N-(3-hydroxypropyl) (meth) acrylamide; N-[3-(dimethylamino)]propyl acrylamide, N,N-dimethyl (meth) acrylamide, N,N-diethyl (meth) acrylamide, N,N-di-n-propyl (meth) acrylamide, N,N-diisopropyl (meth) acrylamide, N,N-di-n-butyl (meth) acrylamide, N,N-diisobutyl (meth) acrylamide, N-(meth) acryloyl morpholine, allyl (meth) acrylamide, 2-ethylhexyl (meth) acrylamide, and diacetone acrylamide. These monofunctional polymerizable compounds (b1) may be used alone or in combination of two or more.
[0035] As for the polyfunctional polymerizable compound (b2), examples of the polyfunctional (meth)acrylate include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, ditetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,7-heptanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, hydroxypivalic acid neopentyl glycol di(meth)acrylate, dicyclopentanyl di(meth)acrylate, caprylic acid acrylate, and the like. Monomers and oligomers such as ester-modified dicyclopentenyl di(meth)acrylate, ethylene oxide-modified phosphoric acid di(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol tetra(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, ethylene oxide-modified bisphenol A di(meth)acrylate, propylene oxide-modified bisphenol A di(meth)acrylate, cyclohexanedimethanol di(meth)acrylate, acrylate (dioxanediol diacrylate), alkoxylated hexanediol di(meth)acrylate, alkoxylated cyclohexanedimethanol di(meth)acrylate, epoxy (meth)acrylate, and urethane (meth)acrylate.
[0036] As for the polyfunctional polymerizable compound (b2), examples of the polyfunctional (meth)acrylamide include methylenebis(meth)acrylamide, ethylenebis(meth)acrylamide, N,N'-(2-methylpropane-1,1-diyl)di(meth)acrylamide, N,N'-cyclohexylmethylenebis(meth)acrylamide, N,N'-(pentane-1,1-diyl)di(meth)acrylamide, N,N'-(3-methylbutane-1,1-diyl)di(meth)acrylamide, 2-(meth)acrylamide-2-methylpropanesulfonic acid, 1,4-bis(acryloyl)piperazine, di-trimethylolpropane tetraacrylamide, dipentaerythritol hexamethylacrylamide, etc. These polyfunctional polymerizable compounds (b2) may be used alone or in combination of two or more.
[0037] One embodiment of the present disclosure is the above-mentioned various curable compositions (D) further containing a polymerizable polymerization initiator (C), and containing 0.1 mass % to 20 mass % of C relative to the total mass of the curable composition. The polymerizable polymerization initiator (C) is a compound other than multifunctional (meth)acrylamide (A) and polymerizable compound (B) having one or more polymerizable groups and one or more polymerization initiating functional groups (starting groups) in the molecule. The polymerizable group of C is one or more groups selected from the group consisting of (meth)acrylate group, (meth)acrylamide group, vinyl group, vinyl ether group, methyl vinyl ether group, allyl group, (meth)allyl ether group, maleimide group, α-substituted maleimide group, α, β-substituted maleimide group. The starting group of C is not particularly limited as long as it generates free radicals, cations, anions, etc. belonging to growth active species by light irradiation or heating. For example, in the case of active energy line curing reaction such as UV and EB, examples include: intramolecular cleavage type that generates free radicals by intramolecular cleavage after absorbing UV light, hydrogen abstraction type that generates free radicals by exchange of hydrogen or electrons, and electron donation type starting groups. More specifically, the starting group of the intramolecular cleavage type can be exemplified by: benzoin derivatives, benzil ketal, α-hydroxyacetophenone, α-aminoacetophenone, acylphosphine oxide, titanocene and 0-acyl oxime type. The starting group of the hydrogen abstraction type can be exemplified by: diphenyl ketone, alkyl diaminodiphenyl ketone, 4,4'-bis (dimethylamino) diphenyl ketone, 4-benzoyl-4'-methyldiphenyl sulfide and other diphenyl ketone derivatives having a diaryl ketone skeleton, 2-hydroxythioxanthone and other thioxanthone derivatives having a thioxanthone skeleton. One or more of these starting groups can be selected and used in combination with one or more of the above-mentioned polymerizable groups. Among them, the hydrogen abstraction type initiator is preferred because it does not produce low molecular weight compounds as by-products or remain in the cured product after the free radical generation reaction. In addition, it is more preferred to have a structure in which a hydrogen abstraction type initiator is combined with a (meth) acrylate group or (meth) acrylamide group, which is a highly polymerizable group. Furthermore, in an aqueous curable composition, it is particularly preferred to use a water-soluble or hydrophilic polymerizable polymerization initiator (C).
[0038] The content of polymerizable polymerization initiator (C) varies according to the structure of the starting group or the type of polymerizable group, the composition of the curable composition, etc., but if it contains more than 0.1% by mass relative to the gross mass of the curable composition, thermal polymerization, photopolymerization or active energy line curing, etc. can be started immediately, and the curable composition can be fully cured. In addition, (C) has a polymerizable group, so if the content of (C) is less than 20% by mass, the curable composition is rapidly cured, and the physical properties of the cured product are not reduced. In order to preferably adjust the physical properties of the cured product according to various uses, the content of the polymerizable polymerization initiator (C) relative to the overall curable composition is preferably 0.5% by mass to 15% by mass, more preferably 1% by mass to 10% by mass.
[0039] One embodiment of the present disclosure is the above-mentioned various curable compositions (D) further containing quaternary salt monomers. The quaternary salt monomer is a compound other than the multifunctional (meth)acrylamide (A) and the polymerizable compound (B), and is a compound having both a polymerizable group and a quaternary salt structure in the molecule, and may be monofunctional or multifunctional. The polymerizable group of the quaternary salt monomer is one or more groups selected from the group consisting of (meth)acrylate group, (meth)acrylamide group, vinyl group, vinyl ether group, methyl vinyl ether group, allyl group, (meth)allyl ether group, maleimide group, α-substituted maleimide group, α, β-substituted maleimide group. The quaternary salt structure may be cationic, anionic, or amphoteric with both cationic and anionic properties. The quaternary salt monomer may be selected from ammonium salts, imidazolium salts, choline salts, A compound composed of one or more cationic groups and / or anionic groups selected from the group consisting of salts, pyrazolium salts, oxazolium salts, pyridinium salts, pyrrolidine salts, phosphonium salts, carboxylates, sulfonates and phosphates, and one or more groups selected from the above-mentioned various polymerizable groups. Among them, the quaternary ammonium salt monomer has antistatic and antibacterial properties and has the effect of promoting the dissolution or dispersion of the pigment in the ink composition, so it is particularly preferred. These quaternary salt monomers can be used alone or in combination of two or more.
[0040] The quaternary salt monomer is 0.1% to 30% by mass relative to the total mass of the curable composition (D). The quaternary salt monomer has a water-soluble quaternary salt monomer and a water-insoluble quaternary salt monomer, but because the hydrophilicity is high, when the organic curable composition contains less than 30% by mass, the water resistance of the obtained solidified material will not be reduced, so it is preferred. In the curable composition of the water system, if it contains more than 0.1% by mass, the water solubility and water dispersibility of the curable composition are significantly improved, so it is preferred. In addition, from these viewpoints, the quaternary salt monomer content in the curable composition is preferably 0.5% to 25% by mass, more preferably 1% to 20% by mass.
[0041] One embodiment of the present disclosure is a coating composition (hereinafter also referred to as coating agent) containing the above-mentioned various curable compositions. The multifunctional (meth) acrylamide (A) and the polymerizable compound (B) as the necessary constituents of the coating composition can be brought in by the curable composition (D) of each of the above-mentioned embodiments, and can also be added as needed when modulating the coating composition. Preferably, the content of A is 1% to 60% by mass, and the content of B is 20% to 99% by mass relative to the total mass of the coating composition. By combining the amphiphilic A with the hydrophilic or hydrophobic or amphiphilic B, a hydrophilic or hydrophobic or amphiphilic coating composition can be obtained. In addition, although A is water-insoluble, by combining with the water-soluble B, a water-soluble coating composition or a coating composition in an emulsion state that can be stably and uniformly dispersed in water can be obtained. This coating composition can easily adjust the type and content of A and B, so it is excellent in mutual solubility for a wide range of compounds from hydrophobic to water-soluble except A and B, and has high wettability for various materials from organic to inorganic systems, so that the cured film (coating film) obtained by curing the coating composition is uniform without unevenness (mura) and transparency and surface smoothness are high. In addition, A has multiple isopropyloxy groups, so it is possible to impart water resistance to the obtained cured film, and the appearance or surface hardness of the cured film can also be adjusted according to the purpose. For example, A does not produce unevenness on the surface of the cured film by using it together with a monofunctional polymerizable compound (b1) as B, and the appearance such as surface smoothness is improved, and the surface hardness of the cured film is significantly improved by using it together with a multifunctional polymerizable compound (b2) as a polymerizable compound (B). This coating composition can be preferably used for various coating applications such as hard coating applications, vehicle applications, indoor or outdoor building materials applications.
[0042] One embodiment of the present disclosure is an adhesive composition (hereinafter also referred to as adhesive) containing the above-mentioned various curable compositions. (A) and polymerizable compounds (B) as essential constituents of the adhesive composition can be brought in by the curable composition (D) of each of the above-mentioned embodiments, and can also be added as needed when modulating the adhesive composition. Preferably, the content of A is 2% to 50% by mass, and the content of B is 10% to 90% by mass relative to the gross mass of the adhesive composition. A is amphiphilic and has multiple (meth) acrylamide groups. Through the interaction of wettability derived from amphiphilicity and cohesiveness of (meth) acrylamide groups, the adhesive composition is excellent in adhesion and contamination resistance (secondary processing (rework) property that can be peeled off again) for various substrates (from organic materials to inorganic materials). In addition, A is amphiphilic, containing multiple (meth) acrylamide groups with high hydrolysis resistance and isopropylidene with high water resistance and resistance to curing shrinkage, and the adhesive layer or adhesive sheet obtained by curing the adhesive composition by the combination of A and B, and the laminated body formed by laminating the adhesive layer, have good yellowing resistance (including transparency) and durability (moisture and heat resistance). In addition, the adhesive composition of the present embodiment can further contain polymerization initiators such as polymerizable polymerization initiators, non-polymerizable polymerization initiators, photopolymerization initiators, thermal polymerization initiators, various solvents or general monomers from low polarity to high polarity, and various additives, which can be adjusted in the range of low viscosity to high viscosity according to the purpose. This adhesive composition can also be preferably used in optical fields such as adhesives, adhesive layers, and adhesive sheets for optical components. In addition, the obtained adhesive layer and the laminated body composed of the above-mentioned adhesive layer and various substrates can be used as adhesive films or adhesive sheets for electronic materials, optical components, and automotive components.
[0043] The adhesive composition of the present embodiment is coated or formed on a separator or substrate, and then cured by active energy line irradiation, thereby forming an adhesive layer. In addition, in the case of containing an organic solvent in the adhesive composition, it can also be coated or formed on a separator or substrate, irradiated with active energy, and the organic solvent is evaporated (dried) while being cured, but since a more transparent adhesive layer can be obtained, it is preferably heated at a temperature of 60°C to 120°C for 1 minute to 30 minutes to dry it, and then active energy curing is performed. The coating of the adhesive composition can use a common coating film formation method such as a spin coating method, a spray coating method, a blade coating method, a dipping method, a gravure roller, a reverse roller method, a screen printing method, and a rod coater method.
[0044] In addition, an adhesive layer composed of an adhesive composition is used to laminate with various substrates to obtain a laminate. The lamination method may be a transfer method or a roll-to-roll method. The thickness of the adhesive layer in the laminate varies according to various uses, so it is not particularly limited, but is usually 4 μm to 150 μm, preferably about 20 μm to 120 μm when used for automotive components, and about 30 μm to 100 μm is suitable when used for electronic materials or optical components.
[0045] The adhesive composition of the present embodiment and the adhesive layer obtained by the above-mentioned adhesive composition show high adhesion to various materials, so as the substrate to be adhered and the substrate to be laminated, various materials such as organic substrates, inorganic substrates and materials composed of organic / inorganic composite materials ranging from low polar materials to high polar materials can be used. For example, polyolefin resins such as polyethylene and polypropylene, polyester resins such as polyethylene terephthalate and polycarbonate, ABS resins as acrylonitrile-butadiene-styrene copolymers, polyimide resins, acrylic resins such as polyamide resins and polymethyl methacrylate, metals such as steel, stainless steel, copper and aluminum, glass, and mixed materials formed by dispersing silica particles belonging to inorganic materials in polyimide as organic materials. The uses of the various laminates obtained are not particularly limited, for example, electronic material uses, optical component uses or automotive component uses can be cited.
[0046] One embodiment of the present disclosure is an adhesive composition (hereinafter also referred to as adhesive) containing the above-mentioned various curable compositions. The multifunctional (meth) acrylamide (A) and polymerizable compound (B) as the necessary constituents of the adhesive composition can be brought in by the curable composition (D) of the above-mentioned embodiments, and can also be added as needed when modulating the adhesive composition. Preferably, the content of A is 2% to 70% by mass relative to the gross mass of the adhesive composition, and the content of B is 20% to 90% by mass. A is amphiphilic and has multiple (meth) acrylamide groups. Through the interaction of the wettability derived from amphiphilic and the cohesiveness of the (meth) acrylamide group, the adhesive composition can be uniformly and evenly attached to various substrates (from organic materials to inorganic materials) without unevenness, and the adhesion after curing is high, and it can be preferably used in the adhesion of the same material or in the adhesion of heterogeneous materials. In addition, A has multiple isopropyloxy groups and (meth) acrylamide groups, and the cured product (adhesive layer, adhesive laminate, etc.) of the adhesive composition containing A has good hydrolysis resistance and water resistance. A can easily adjust the viscosity of the adhesive composition by using it in combination with a monofunctional polymerizable compound (b1), and can make a thin to thick adhesive layer according to the purpose. By using it in combination with a multifunctional polymerizable compound (b2), the heat resistance and resistance to cold and hot shock of the cured product can be significantly improved. Furthermore, the adhesive composition containing amphiphilic A and various B and polymerizable or non-polymerizable polymerization initiators has high transparency, and the adhesive layer obtained by curing the above-mentioned adhesive composition also maintains high transparency, so this adhesive composition can also be preferably used in optical fields such as adhesives for optical components.
[0047] One embodiment of the present disclosure is an ink composition (hereinafter also referred to as ink) containing the above-mentioned various curable compositions. The multifunctional (meth) acrylamide (A) and the polymerizable compound (B) as the essential components of the ink composition can be brought in by the curable composition (D) of each of the above-mentioned embodiments, and can also be added as needed when the ink composition is prepared. Preferably, the content of A is 3% to 50% by mass, and the content of B is 20% to 85% by mass relative to the total mass of the ink composition. A is amphiphilic, and by mixing with B of various polarities from hydrophilic to hydrophobic, the dispersibility of various inorganic pigments and organic pigments is excellent, and it exhibits excellent coating properties for various printed substrates, and the obtained printed matter has excellent print clarity. The ink composition has high curability by containing A, and the surface drying property of the obtained printed surface is good. In addition, by using A and a multifunctional polymerizable compound (b2) in combination, the surface drying property of the printed surface obtained by the ink composition is further improved. By using A and a monofunctional polymerizable compound (b1) in combination, an ink composition from low viscosity to high viscosity can be obtained. The ink composition of this embodiment can preferably adjust the viscosity according to various uses or printing methods, and the discharge stability and printing accuracy (including printing clarity) during printing are both high. The viscosity of the ink composition is preferably 1000mPa·s or less at 25°C, more preferably 500mPa·s or less, and particularly preferably 100mPa·s or less from the perspective of being preferably used in an inkjet method. After the ink composition is printed on a substrate, it is cured by irradiation with active energy rays or heat to form a printed surface (ink layer or printing layer). Furthermore, the quaternary salt monomer has excellent mutual solubility with the pigment, so by containing a quaternary salt monomer in the ink composition, the dissolution or dispersion of the pigment is promoted. From the perspective of being able to present the viscosity of the ink composition, pigment dispersibility, curability, discharge stability, and surface dryness and clarity of the obtained printed surface in a well-balanced manner, the ink composition preferably contains 3% to 50% by mass of A, 30% to 80% by mass of b1, and 5% to 40% by mass of b2. Such an ink composition can be preferably used in various printing methods such as inkjet printing, lithography, screen printing, and flexographic printing. For example, lithography is a printing method that utilizes the property of the oily lithographic ink composition to repel water, but by containing A and hydrophobic B, the ink composition exhibits high hydrophobicity and high curability, thereby enabling high-speed and high-precision printing. In addition, in the ink composition containing A having a plurality of isopropyloxy groups and hydrophilic B, the water resistance of the obtained printed matter can also be fully satisfactory.
[0048] One embodiment of the present disclosure is an aqueous ink composition (hereinafter also referred to as aqueous ink) containing the above-mentioned various curable compositions. The multifunctional (meth) acrylamide (A) and the polymerizable compound (B) as the essential components of the ink composition can be introduced by the curable composition (D) of each of the above-mentioned embodiments, and can also be added as needed when the aqueous ink composition is prepared. Preferably, the content of A is 1% to 60% by mass, the content of B is 5% to 89% by mass, and the content of water is 10% to 50% by mass relative to the total mass of the aqueous ink composition. A is non-water-soluble and amphiphilic, so it has good miscibility with water-soluble B, and the curable composition obtained by mixing with water-soluble B can be used as an aqueous ink composition. This kind of ink composition has excellent solubility relative to water or excellent miscibility with water. In addition, it has good solubility or dispersibility for water-soluble pigments, etc., and has high storage stability as a transparent ink without pigment, and has high pigment dispersibility and storage stability as an ink containing pigment. In addition, the aqueous ink composition contains A, so it has high curability, and the water resistance of the obtained printed surface is excellent. The mutual solubility of A and B and the mutual solubility of D containing A and B with additives such as water or water-soluble pigments are high, and a variety of inks can be prepared according to the purpose, such as an ink composition with a viscosity range suitable for inkjet printing. In addition, the discharge stability of the ink composition during inkjet printing is also good, and high printing characteristics can be exhibited. Furthermore, in the case of containing 0.1% by mass or more of a quaternary salt monomer, the solubility of A in water is significantly improved, and the above-mentioned various characteristics of the aqueous ink composition and the printed matter as its solidified product are further improved, so it is preferred. The aqueous ink composition of the present embodiment can be in the state of an aqueous solution dissolved in water, or it can be in the state of a water dispersion such as an emulsion dispersed in water. In addition, the content of water is 10% by mass or more relative to the total mass of the aqueous ink composition, preferably 20% by mass or more, and more preferably 30% by mass or more. Water is preferably water that does not contain ionic impurities such as ion exchange water or distilled water.
[0049] One embodiment of the present disclosure is a three-dimensional modeling ink composition (hereinafter also referred to as a modeling ink composition or a modeling ink) containing the above-mentioned various curable compositions. The multifunctional (meth)acrylamide (A) and the polymerizable compound (B) as the essential components of the modeling ink composition can be introduced from the curable composition (D) of each of the above-mentioned embodiments. In addition, they can also be added as needed when preparing the modeling ink composition. Relative to the total mass of the modeling ink composition, the content of A is 1% to 60% by mass, and the content of B is 20% to 99% by mass. A has multiple (meth)acrylamide groups and isopropyloxy groups, and the modeling ink composition has high curability, and the obtained modeling (cured product) has good strength, toughness (impact resistance) and water resistance. By containing a monofunctional polymerizable compound (b1) as B, the viscosity of the modeling ink composition can be preferably adjusted according to the specifications of the device used for modeling, and the operability is also improved. By containing the multifunctional polymerizable compound (b2) as B, the curability of the ink composition for molding, the strength and hardness of the obtained molding, etc. can be further improved. When the absolute value of the difference in the SP value between A and B is 3.0 or less, the mutual solubility of A and B is high, the transparency of the ink composition for molding, and the ink discharge stability during molding are high. In addition, when the acrylic acid equivalent of A is 180 or more, the curing shrinkage resistance of the ink composition for molding is higher, and a molding with excellent molding accuracy can be obtained.
[0050] The ink composition for shaping is formed into a thin film by curing it by irradiation with active energy rays or heat while being formed into a predetermined shape pattern or just after being formed, and a three-dimensional object can be obtained by laminating the above-mentioned thin film. The shaping method is not particularly limited, and for example, a photoforming method in which the ink is discharged by inkjet and cured by irradiation with active energy rays can be cited. In this case, from the perspective of discharge stability, the viscosity of the ink composition for shaping at 25°C is preferably 1mPa·s to 200mPa·s, and the discharge temperature is preferably in the range of 20°C to 100°C. From the perspective that the obtained three-dimensional object can present strength, shaping accuracy and impact resistance in a well-balanced manner, it is more preferred that the ink composition for shaping contains 5% to 60% by mass of A, 10% to 70% by mass of b1, and 5% to 50% by mass of b2.
[0051] One embodiment of the present disclosure is an aqueous coating composition (hereinafter also referred to as aqueous coating) containing the above-mentioned various curable compositions. Multifunctional (methyl) acrylamide (A) and polymerizable compound (B) as the essential constituents of the aqueous coating composition can be brought in by the curable composition (D) of the above-mentioned various embodiments, and can also be added as needed when modulating the aqueous coating composition. Preferably, relative to the gross mass of the aqueous coating composition, the content of A is 1% to 50% by mass, the content of B is 5% to 79% by mass, and the content of water is 20% to 80% by mass. A is non-water-soluble and amphiphilic, so it has good mutual solubility with water-soluble B, and the curable composition obtained by mixing with water-soluble B can be used as an aqueous coating composition. This coating composition presents excellent solubility for water or excellent mutual solubility with water, and in addition, presents good solubility or dispersibility for water-soluble pigments, etc., as a transparent ink without pigment, it has high storage stability, and as an ink containing pigment, it has a high degree of pigment dispersibility and storage stability. In addition, the water-based coating composition contains A, so it has high curability, and the water resistance of the obtained coating film is excellent. The mutual solubility of A and B and the mutual solubility of D containing A and B with additives such as water or water-soluble pigments are high, and A has multiple (methyl) acrylamide groups and isopropyloxy groups in the lump, so the wettability and adhesion of various substrates such as wood, metal, concrete, rubber, pottery, plastic, paper, fiber, non-woven fabrics are high, and can be used for the coating of multiple materials. And then, in the case of containing 0.1% by mass or more of the quaternary salt monomer, A significantly improves the solubility of water, and in the water-based coating composition and the coating film as its solidified product, the above-mentioned various characteristics are further improved, so it is preferred. The water-based coating composition of the present embodiment can be the state of the aqueous solution dissolved in water, and can also be the state of water dispersion such as the emulsion dispersed in water. In addition, the content of water is more than 20% by mass relative to the gross mass of the water-based coating composition, preferably more than 30% by mass, and more preferably more than 50% by mass. Water is preferably water without ionic impurities such as ion exchange water or distilled water.
[0052] The water-based coating composition of the present embodiment may contain an organic solvent as required, and the content of the organic solvent is 40% by mass or less relative to the total mass of volatile components (the total of organic solvent and water), and is preferably 30% by mass or less, more preferably 20% by mass or less.After the water-based coating composition is applied, coated or film-formed on a barrier film or substrate, active energies such as UV or EB are irradiated, so that the organic solvent and water are evaporated (dried) while being cured, but due to the higher coating film of transparency that can be obtained, it is preferably heated at a temperature of 60°C to 120°C for 1 minute to 30 minutes to make it dry, and then active energy curing is carried out.The coating of the water-based coating composition can use the common film formation methods such as spin coating, spray coating, blade coating, dipping, immersion, gravure roller, reverse roll method, screen printing, rod coater method, and in addition, it can also be preferably used for the coating of the manual operation using a roller brush or a brush, a spatula, etc.
[0053] One embodiment of the present disclosure is a sealant composition (hereinafter also referred to as a sealant). The multifunctional (meth) acrylamide (A) and the polymerizable compound (B) as the essential constituents of the sealant composition can be brought in by the curable composition (D) of each of the above embodiments, and can also be added as needed when the sealant composition is modulated. Preferably, the content of A is 1% to 60% by mass, and the content of B is 10% to 99% by mass relative to the total mass of the sealant composition. The (meth) acrylamide group of A has high curability for both active energy lines and heat, and the sealant composition obtained by using A and B together also exhibits high curability. In addition, A is multifunctional, so there are very few uncured polymerizable compounds (residual monomers) in the cured product such as the sealing layer or sealant formed by curing the sealant composition, and the cured product has high degassing resistance, resistance to wet heat yellowing, corrosion resistance, etc., and can show excellent sealing effect as a sealant. A and B have high mutual solubility, and the sealant composition and the cured products such as the sealant layer formed by curing the sealant composition have good transparency and can also be suitably used for optical purposes. The multiple isopropylidene groups of A have the effect of making the obtained cured product have water resistance and curing shrinkage resistance, and further, the workability of the sealant composition is improved by the combined use of A and the monofunctional polymerizable compound (b1), and the curability of the sealant composition, the strength of the obtained cured product and the heat-resistant sealing properties are improved by the combined use of A and the multifunctional polymerizable compound (b2).
[0054] One embodiment of the present disclosure is a nail cosmetic composition (hereinafter also referred to as nail cosmetic). The multifunctional (meth) acrylamide (A) and polymerizable compound (B) as the essential components of the nail cosmetic composition can be introduced by the curable composition (D) of each of the above embodiments, and can also be added as needed when the nail cosmetic composition is prepared. Preferably, the content of A is 1% to 40% by mass, and the content of B is 10% to 99% by mass relative to the total mass of the nail cosmetic composition. A has multiple (meth) acrylamide groups, and the curability of the obtained nail cosmetic composition and the adhesion to the nail are high, and the strength of the obtained solidified product (also referred to as a cured film or nail) is also high. The mutual solubility of A and B and the mutual solubility of A and B and other components such as pigments are all high, so the transparency and surface glossiness of the nail cosmetic composition and its cured film without pigment are high, and the pigment dispersion (uniformity) of the nail cosmetic composition containing pigment is high, and the surface glossiness of the obtained cured film is high, and the cured film formed by overlapping coating or repairing operation is almost uneven. In addition, when the acrylic acid equivalent of A is 180 or more, the nail cosmetic composition has better resistance to curing shrinkage, no unevenness is generated on the surface of the cured film, and the appearance of the nail is good. By appropriately adjusting the type and content of A and the monofunctional polymerizable compound (b1) and / or the polyfunctional polymerizable compound (b2), a nail cosmetic composition that can be used for various substrates such as natural nails, artificial nails, nail films or nail sheets can be obtained.
[0055] One embodiment of the present disclosure is a dental material composition (hereinafter also referred to as dental material). Multifunctional (meth) acrylamide (A) and polymerizable compound (B) as essential components of the dental material composition can be brought in by the curable composition (D) of each of the above embodiments, and can also be added as needed when modulating the dental material composition. Preferably, the content of A is 0.5% by mass to 50% by mass, and the content of B is 5% by mass to 99% by mass relative to the gross mass of the dental material composition. A has multiple (meth) acrylamide groups, and the curability and adhesion of the dental material composition are both high, and high adhesion can be obtained when used as a dental material for subsequent use. In addition, when the acrylic acid equivalent of A is more than 180, the dental material composition has high resistance to curing shrinkage, no deformation after curing or surface concave-convex, and good surface smoothness. A and B have high mutual solubility, and the dispersibility of white pigment or inorganic filler is excellent. As a composite resin, filler or covering for treating or repairing natural teeth, it can also be suitably used as a dental material used in the production of artificial teeth such as dentures, dental bridges, and implants. Furthermore, the viscosity of the dental material composition can be easily adjusted by using A in combination with the monofunctional polymerizable compound (b1), thereby improving the workability. The curability of the dental material composition can be further improved by using A in combination with the multifunctional polymerizable compound (b2), and the hardness of the obtained cured product can also be increased.
[0056] One embodiment of the present disclosure is a decorative coating composition (hereinafter also referred to as a decorative coating). The multifunctional (meth) acrylamide (A) and the polymerizable compound (B) as the essential components of the decorative coating composition can be introduced from the curable composition (D) of each of the above embodiments, and can be added as needed when the decorative coating composition is prepared. Preferably, the content of A is 1% to 50% by mass, and the content of B is 20% to 99% by mass relative to the total mass of the decorative coating composition. A has multiple (meth) acrylamide groups, and the obtained decorative coating composition has high curability, and the obtained decorative coating, decorative film, decorative film and other cured products have good surface hardness and scratch resistance. In addition, A has multiple isopropyloxy groups, and the obtained cured product shows flexibility, and the decorative coating or decorative film, decorative film has excellent bending resistance. A is amphiphilic, has high solubility with B, and oligomers or polymers can be further dissolved in D containing A and B, so that the elongation of the cured product obtained by this composition becomes higher.
[0057] In each embodiment of the present disclosure, the curable composition (D) may also contain components other than the above as arbitrary components as needed. As an arbitrary component, an organic solvent or various additives may be used as needed. As an organic solvent, there can be mentioned: alcohols such as ethanol, n-propanol, and isopropanol; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; alkanediols; polyalkylene glycols; glycol ethers; glycol esters; aromatic hydrocarbons such as benzene, toluene, ethylbenzene, and xylene; aliphatic hydrocarbons such as hexane, heptane, octane, decane, and cyclohexane; esters such as ethyl acetate, butyl acetate, and 2-hydroxyethyl acetate; acetonitrile, N, N-dimethylformamide. These organic solvents can be used alone or in combination of two or more. Especially, in the curable composition of organic system, just when coating, film-making, shaping or after shaping, by drying and other methods and easy to remove viewpoint, more preferably low boiling point ethyl acetate, methyl ethyl ketone, acetone etc., in aqueous curable composition, more preferably low boiling point water-soluble ethanol, n-propanol, isopropanol etc..In addition, when containing organic solvent, the content of this organic solvent is preferably 1.0 mass % to 50 mass %, more preferably 5 mass % to 30 mass % relative to the gross mass of curable composition.If within this range, then will not give the composition of each embodiment of the present disclosure and make these compositions solidify and the desired properties of the solidified material obtained cause adverse effects.
[0058] As additives used in the present disclosure, there can be cited: polymerization initiators (except polymerizable polymerization initiators (C)), thermal polymerization inhibitors, anti-aging agents, antioxidants, ultraviolet sensitizers, preservatives, phosphates and other flame retardants, surfactants, wetting and dispersing materials, antistatic agents, colorants, plasticizers, surface lubricants, leveling agents, softeners, pigments, organic fillers, inorganic fillers, silica particles, etc. The amount of these additives added is not particularly limited as long as it does not adversely affect the properties expected by the compositions of each embodiment of the present disclosure and the cured products obtained by curing the compositions. With respect to the total mass of the curable composition, it is preferably 5% by mass or less, and more preferably 2% by mass or less.
[0059] In each embodiment of the present disclosure, non-polymerizable components may be further contained as needed. Non-polymerizable components are compounds that do not contain the above-mentioned polymerizable groups in the molecule. Regarding non-polymerizable components, if classified according to molecular weight (weight average molecular weight (Mw)), when Mw is 1,000 or more but less than 10,000, it is set as a non-polymerizable oligomer, and when Mw is 10,000 or more, it is set as a non-polymerizable polymer. As non-polymerizable oligomers and non-polymerizable polymers, thermoplastic resins, rosin-based resins or mixtures of these resins may be cited. As the above-mentioned thermoplastic resins, for example, (meth) acrylic resins, cyclic polyolefin resins, cellulose resins, polyester resins, polyurethane resins, polysulfonic acid resins, ABS resins as copolymers of acrylonitrile, butadiene and styrene, polycarbonate resins, polyamide resins, polyimide resins may be cited. In addition, examples of rosin-based resins include natural rosins such as gum rosin, and modified rosin resins such as hydrogenated rosin obtained by modifying natural rosin, disproportionated rosin, rosin-modified phenolic resin, maleic acid-modified rosin resin, maleated rosin, and esterified rubber. These non-polymerizable oligomers and non-polymerizable polymers may be used alone or in combination of two or more.
[0060] The content of the non-polymerizable component is preferably 0.1% to 20% by mass relative to the total mass of the curable composition. The non-polymerizable component has the following functions: adjusting the viscosity of the curable composition; improving the adhesion of the adhesive composition and the adhesive composition to the substrate; improving the adhesion of the adhesive layer or the adhesive; and giving toughness to the cured product of the coating composition, the ink composition and the three-dimensional shaping ink composition, the sealant composition, and the decorative coating composition. From these viewpoints, the content of the non-polymerizable component is more preferably 0.5% to 15% by mass, and particularly preferably 1% to 10% by mass.
[0061] The curable composition of each embodiment of the present disclosure can be cured by active energy rays such as UV or EB and / or heat, and a cured product that can be preferably used for various purposes can be obtained. For example, as an adhesive composition, after the curable composition is applied to a release film or various substrates, it is cured by active energy rays, thereby forming an adhesive layer. In the present disclosure, the situation in which the curable composition is cured by active energy rays and heat is also referred to as mixed curing. In mixed curing, curing can be carried out in the order of active energy rays and heat, or in the order of heat and active energy rays. Thermal curing using the heat generated during active energy ray curing can also be performed, that is, simultaneous curing of active energy rays and heat is performed.
[0062] As the above-mentioned active energy line, it is defined as an energy line that can decompose the compound (photopolymerization initiator) that produces active species to produce active species. As such active energy lines, for example, visible light, ultraviolet light, infrared light, α-rays, β-rays, γ-rays, X-rays, electron beams (EB), etc. can be cited. In the case of using electron beams as active energy lines, photopolymerization initiators may not be used. On the other hand, in the case of using ultraviolet light or visible light, it is preferred to use photopolymerization initiators. The irradiation of active energy lines is preferably carried out in an inert gas atmosphere such as nitrogen or carbon dioxide or in an atmosphere in which the oxygen concentration is reduced, but the curable composition of each embodiment of the present disclosure has a multifunctional (meth) acrylamide (A), so the curing property is good and it can be fully cured even in a normal air atmosphere. The irradiation temperature of the active energy line is preferably 10°C to 200°C, and the irradiation time is preferably 1 second to 60 minutes.
[0063] The non-polymerizable photopolymerization initiator may be any substance that generates radicals (ie, a photoradical polymerization initiator) by irradiation with ultraviolet rays of an appropriate wavelength that can cause a polymerization reaction of the component, depending on the type of the active energy ray-reactive component. Such a photopolymerization initiator may be appropriately selected from common photopolymerization initiators such as acetophenone-based, benzoin-based, diphenyl ketone-based, and thioxanthone-based photopolymerization initiators. As commercially available products, Omnirad 1116, Omnirad 1173, Omnirad 184, Omnirad 369, Omnirad 500, Omnirad 651, Omnirad 754, Omnirad 819, Omnirad 907, Omnirad 1300, Omnirad 1800, Omnirad 1870, Omnirad 2959, Omnirad 4265, Omnirad TPO, Omnipol 2702, Omnipol 910, Omnipol 9210, Omnipol 2702, Omnipok BP, Omnipol TP, Omnipol TX, etc., SpeedCure 7005, Speed Cure 7010, etc. manufactured by Arkema, FOM-03011, etc. manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., EBECR YL P36, etc. manufactured by UCB. These non-polymerizable photopolymerization initiators may be used alone or in combination of two or more.
[0064] The non-polymerizable photoradical polymerization initiator is not particularly limited, and examples thereof include: benzoins such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and anisole methyl ether; acetophenones such as 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone, α-hydroxy-α,α'-dimethylacetophenone, methoxyacetophenone, 2,2'-dimethoxy-2-phenylacetophenone, 2-hydroxy-2-cyclohexylacetophenone, 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, and 4-tert-butyldichloroacetophenone; 2-hydroxy-2-methylpropiophenone, 2-hydroxy-4'-isopropyl-2-methylpropiophenone, and 2-hydroxy-4'-isopropyl-2-methylpropiophenone. 1-Hydroxy-1-nitropropenoic acid esters; ... These non-polymerizable photoradical polymerization initiators may be used alone or in combination of two or more.
[0065] The content of the non-polymerizable photopolymerization initiator is 0.1% to 20% by weight relative to the total mass of the curable composition of each embodiment of the present disclosure, preferably 0.5% to 10% by weight, and more preferably 1% to 5% by weight. If the content of the non-polymerizable photopolymerization initiator is less than 0.1% by weight, sufficient curability cannot be obtained. If it exceeds 20% by weight, the strength and other properties of the cured product are sometimes reduced. In addition, the polymerizable photopolymerization initiator (C) and the non-polymerizable photopolymerization initiator can be used together.
[0066] The thermal curing of the curable composition of each embodiment of the present disclosure can be carried out by a known method in the presence of a thermal polymerization initiator, for example, by emulsion polymerization, solution polymerization, suspension polymerization, block polymerization and other methods, a cross-linked cured product can be obtained. In the case of solution polymerization, the solvents that can be used include: aromatic hydrocarbons such as toluene, ethylbenzene, and xylene; aliphatic hydrocarbons such as hexane, heptane, octane, decane, and cyclohexane; esters such as ethyl acetate, butyl acetate, and 2-hydroxyethyl acetate; aliphatic alcohols such as ethanol, n-propanol, and isopropanol; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; acetonitrile, N, N-dimethylformamide, etc. These solvents can be used alone or in combination of two or more. In particular, from the perspective of easy removal of the cured product, it is preferred to use low-boiling ethyl acetate, methyl ethyl ketone, acetone, etc. The temperature or time of thermal polymerization varies depending on the thermal polymerization method adopted and the thermal polymerization initiator used, and is usually calculated based on the half-life of the initiator. The temperature is usually preferably 60°C to 120°C, and the time is usually preferably 2 hours to 20 hours, more preferably 5 hours to 10 hours.
[0067] As a thermal polymerization initiator, a thermal free radical polymerization initiator can be exemplified, and azobisisobutyronitrile, azobisvaleronitrile, azobis(isobutyric acid) dimethyl ester, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] tetrahydrate, 2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2'-azobis[2-(2-imidazoline-2-yl)propane] and other azo compound catalysts, or peroxide catalysts such as benzoyl peroxide and hydrogen peroxide, ammonium persulfate, sodium persulfate and other persulfate catalysts can be used. The content of the thermal polymerization initiator is about 0.01% to 10% by mass relative to the gross mass of the curable composition. Furthermore, conventional free radical polymerization techniques such as the adjustment of the molecular weight of a chain transfer agent can be applied.
[0068] [Example]
[0069] The present disclosure is described in more detail with reference to the following examples and comparative examples, but the present disclosure is not limited to the following examples. The abbreviations of the components described in the examples and comparative examples are as follows. In addition, unless otherwise specified, all "parts" and "%" are based on mass. In addition, the unit of SP value (cal / cm 3 ) 1 / 2 .
[0070] Various compounds and materials described in Examples and Comparative Examples are as follows.
[0071] (1) Multifunctional (meth)acrylamide (A)
[0072] A-1: polypropyleneoxy dimethyl acrylamide (D400) (n = integer from 1 to 2, SP value = 10.6, average molecular weight = 366, acrylic acid equivalent = 183)
[0073] A-2: Polypropyleneoxydiacrylamide (D400) (n=integer of 2 to 3, SP value=10.4, average molecular weight=400, acrylic acid equivalent=200)
[0074] A-3: Polypropyleneoxybisacrylamide (D2000) (n=33, SP value=9.0, average molecular weight=2100, acrylic acid equivalent=1050)
[0075] A-4: polypropyleneoxybisacrylamide (D4000) (n=67, SP value=8.8, average molecular weight=4100, acrylic acid equivalent=2050)
[0076] A-5: trimethylolpropane polypropyleneoxy triacrylamide (D600) (x2=integer of 1 to 2, y2=integer of 1 to 2, z2=integer of 1 to 2, x2+y2+z2=5 to 6, m=1, SP value=10.5, average molecular weight=600, acrylic acid equivalent=200)
[0077] A-6: trimethylolpropane polypropyleneoxy triacrylamide (D3000) (x2=integer from 1 to 20, y2=integer from 1 to 10, z2=integer from 1 to 20, x2+y2+z2=50, m=0, SP value=9.0, average molecular weight=3200, acrylic acid equivalent=1067)
[0078] A-7: trimethylolpropane polypropyleneoxy triacrylamide (D5000) (x2=integer from 1 to 30, y2=integer from 1 to 25, z2=integer from 1 to 30, x2+y2+z2=84, m=0, SP value=8.9, average molecular weight=5200, acrylic acid equivalent=1733)
[0079] A-8: polypropyleneoxypolyethyleneoxydiacrylamide (D700) (x1=integer of 1 to 2, y1=integer of 1 to 9, z1=integer of 1 to 2, x1+z1=integer of 2 to 4, SP value=10.0, average molecular weight=700, acrylic acid equivalent=350)
[0080] A-9: polypropyleneoxypolyethyleneoxydiacrylamide (D1000) (x1=integer of 1 to 3, y1=integer of 1 to 13, z1=integer of 1 to 3, x1+z1=integer of 2 to 6, SP value=9.7, average molecular weight=1000, acrylic acid equivalent=500)
[0081] A-10: polypropyleneoxypolyethyleneoxydiacrylamide (D2000) (x1=integer of 1 to 3, y1=integer of 1 to 39, z1=integer of 1 to 3, x1+z1=integer of 2 to 6, SP value=9.5, average molecular weight=2100, acrylic acid equivalent=1050)
[0082] A-11: Pentaerythritol polypropyleneoxytetraacrylamide (D800) (x3=integer from 1 to 3, y3=integer from 1 to 3, z3=integer from 1 to 3, s3=integer from 1 to 3, x3+y3+z3+s3=8, SP value=10.7, average molecular weight=813, acrylic acid equivalent=203)
[0083] (2) Polymerizable compound (B)
[0084] (2-1) Monofunctional polymerizable compound (b1)
[0085] b1-1: Acryloylmorpholine (registered trademarks "Kohshylmer" and "ACMO", SP value = 11.2, water-soluble)
[0086] b1-2: N-hydroxyethylacrylamide (registered trademarks "Kohshylmer" and "HEAA", SP value = 14.4, water-soluble)
[0087] b1-3: dimethylacrylamide (registered trademarks "Kohshylmer" and "DMAA", SP value = 10.6, water-soluble)
[0088] b1-4: Diethylacrylamide (registered trademarks "Kohshylmer" and "DEAA", SP value = 10.1, water-soluble)
[0089] b1-5: Isopropyl acrylamide (registered trademarks "Kohshylmer" and "NIPAM", SP value = 10.6, water-soluble)
[0090] b1-6: diacetone acrylamide (registered trademark "Kohshylmer", SP value = 10.7, water-soluble)
[0091] b1-7: N,N-dimethylamidopropyl acrylamide (registered trademarks "Kohshylmer" and "DMA PAA", SP value = 10.3, water-soluble)
[0092] b1-8: N-hydroxyethyl methacrylamide (registered trademark "Kohshylmer", SP value = 13.8, water-soluble)
[0093] b1-9: N-methyl-N-hydroxyethyl acrylamide (registered trademark "Kohshylmer", SP value = 13.3, water-soluble)
[0094] b1-10: N-octylacrylamide (registered trademark "Kohshylmer", SP value = 9.9, water-insoluble)
[0095] b1-11: Isobornyl acrylate (SP value = 8.7, water-insoluble)
[0096] b1-12: 4-tert-butylcyclohexyl acrylate (registered trademark "Kohshylmer", SP value = 8.7, water-insoluble)
[0097] b1-13: Butyl acrylate (SP value = 8.8, water-insoluble)
[0098] b1-14: 2-ethylhexyl acrylate (SP value = 8.6, water-insoluble)
[0099] b1-15: Tetrahydrofurfuryl acrylate (SP value = 9.5, water-soluble)
[0100] b1-16: Hydroxyethyl acrylate (SP value = 12.5, water-soluble)
[0101] b1-17: 4-Hydroxybutyl acrylate (SP value = 11.7, water-soluble)
[0102] b1-18: Phenoxyethyl acrylate (SP value = 10.1, water-insoluble)
[0103] b1-19: Acrylic acid (SP value = 11.1, water-soluble)
[0104] b1-20: Isobornyl methacrylate (SP value = 8.7, water-insoluble)
[0105] b1-21: Acryloylaminoethyltrimethylammonium trifluoromethanesulfonate (SP value = 8.3, water-insoluble)
[0106] b1-22: Acryloylaminopropyltrimethylammonium bis(trifluoromethanesulfonyl)imide (SP value = 11.1, water-insoluble)
[0107] (2-1) Polyfunctional polymerizable compound (b1)
[0108] b2-1: 1,6-hexanediol diacrylate (SP value = 9.6, water-insoluble)
[0109] b2-2: dipentaerythritol hexaacrylate (SP value = 10.4, water-insoluble)
[0110] b2-3: Polyethylene glycol 400 diacrylate (SP value = 9.6, water-soluble)
[0111] b2-4: Pentaerythritol triacrylate (SP value = 11.5, water-insoluble)
[0112] b2-5: bifunctional urethane acrylate UV-3000B (estimated SP value = 10.0 (reference polyurethane SP value), water-insoluble)
[0113] b2-6: bifunctional urethane acrylate UV-6640B (estimated SP value = 10.0 (reference polyurethane SP value), water-insoluble)
[0114] b2-7: Methylenebisacrylamide (SP value = 13.4, water-soluble)
[0115] (3) Polymerizable polymerization initiator (C)
[0116] C-1: 2-[4-(2-hydroxy-2-methylpropionyl)phenoxy]ethyl acrylate (water-insoluble)
[0117] C-2: 2-phenylbenzoylmethyl acrylate (water-insoluble)
[0118] C-3: 4-Acryloyloxybenzophenone (water-insoluble)
[0119] C-4: Kohshyex-I 3002 (polymer type, water-insoluble) (registered trademark "Kohshye x", manufactured by KJ Chemicals Co., Ltd.)
[0120] (4) Other ingredients (E)
[0121] (4-1) Additives (non-polymerizable polymerization initiators, sensitizers, pigments, etc.)
[0122] E1-1: Omnirad 2595 (water-soluble photopolymerization initiator)
[0123] E1-2: Omnirad TPO (water-insoluble photopolymerization initiator)
[0124] E1-3: Omnirad 1173 (water-insoluble photopolymerization initiator)
[0125] E1-4: Tackifier KE-359 (non-polymerizable hydrogenated rosin, manufactured by Arakawa Chemical Industries, Ltd.)
[0126] E1-5: Carbon black (pigment, CI Pigment Black 7)
[0127] E1-6: Solsperse 6000 (pigment dispersant, manufactured by Lubrizol Japan)
[0128] E1-7: 2,4-diethylthioxanthone (sensitizer, manufactured by Lambson)
[0129] E1-8: BYK-377 (polysilicone-based surface conditioning agent, solid content 100%, manufactured by BYK-Chemie Japan)
[0130] E1-9: Antox MS60 (sulfonate emulsifier, manufactured by Nippon Emulsifier Co., Ltd.)
[0131] E1-10: 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] tetrahydrate (water-soluble, thermal polymerization initiator)
[0132] v1-11: Pigment blue 15:4 (water-soluble pigment, manufactured by TOYOCOLOR)
[0133] v1-12: BYKJET-9151 (water-soluble pigment dispersant, manufactured by BYK)
[0134] v1-13: Inorganic filler (titanium oxide)
[0135] (4-2) Organic solvents, quaternary salt monomers, etc.
[0136] E2-1: Ethyl acetate
[0137] E2-2: Methyl ethyl ketone
[0138] E2-3: Toluene
[0139] E2-4: Acryloylaminopropyltrimethylammonium p-toluenesulfonate
[0140] E2-5: Acryloyloxyethyltrimethylammonium bis(trifluoromethanesulfonyl)imide
[0141] (5) Water-soluble multifunctional (meth)acrylamide and water-insoluble multifunctional (meth)acrylate
[0142] F-1: Polyethylene glycol diacrylamide (n=2) (molecular weight=256, acrylic acid equivalent=128, SP value=11.8, water-soluble)
[0143] F-2: N-[tris(3-acrylamidopropoxymethyl)methyl]acrylamide (molecular weight = 508, acrylic acid equivalent = 127, SP value = 12.1, water-soluble)
[0144] F-3: N,N'-[oxybis(2,1-ethanedioxy-3,1-propanediyl)]bisacrylamide (molecular weight = 328, acrylic acid equivalent = 164, SP value = 11.1, water-soluble)
[0145] F-4: tripropylene glycol diacrylate (n=3) (molecular weight=300, acrylic acid equivalent=150, SP value=9.3, water-insoluble)
[0146] (6) Abbreviation of evaluation substrate
[0147] PET: Easy-to-bond polyethylene terephthalate sheets and films
[0148] PMMA: Polymethyl methacrylate sheets and films
[0149] PC: Polycarbonate sheet and film
[0150] PVC: Polyvinyl chloride sheet and film
[0151] ABS: Acrylonitrile-butadiene-styrene copolymer synthetic resin sheet
[0152] GL: Glass Plate
[0153] AL: Aluminum Plate
[0154] Examples 1 to 15 and Comparative Examples 1 to 6 (Preparation and Evaluation of Curable Compositions)
[0155] The polyfunctional (meth)acrylamide (A), the polymerizable compound (B) and other components were weighed in the mass ratio shown in Table 1, and mixed at 35°C for 1 hour to prepare curable compositions of Examples 1 to 15 and Comparative Examples 1 to 6. The transparency (miscibility) and active energy ray curability of the obtained curable compositions were evaluated by the following methods, and the results are shown in Table 1. In addition, the absolute value of the difference between the SP values of A and B and the SP values of A and B are summarized in Table 1.
[0156] Evaluation of transparency (miscibility) of curable composition
[0157] The various curable compositions obtained were left to stand at 23° C. overnight, and the state of the compositions was visually observed. Transparency was evaluated by four levels as described below.
[0158] ⊚: High transparency, and no turbidity or separation was observed.
[0159] ○: High transparency, but slightly turbid.
[0160] Δ: Layer separation did not occur, but white turbidity occurred.
[0161] ×: White turbidity occurred, and further layer separation occurred.
[0162] Evaluation of active energy ray curability of curable composition
[0163] The easy-bonding surface of a 100 μm thick PET film (manufactured by Toyobo Co., Ltd., polyester film COSMOSHINE A4100) was placed in close contact with a horizontally arranged glass plate, and the curable composition of each embodiment and comparative example was applied using a rod coater (No. 12) so that the thickness of the coating film after drying became 20 μm. After heating at 60° C. for two minutes, ultraviolet rays were irradiated (device: manufactured by Aitec System Co., Ltd., desktop batch UV-LED curing device MUVBA-0.3×0.3×0.5, wavelength 405 nm, illumination (UV-V) 50 mW / cm 2 ) to cure the curable composition. Then, the presence or absence of stickiness on the surface of the cured film was confirmed, and ultraviolet irradiation was performed additionally until the stickiness disappeared, and the curability was evaluated according to the following criteria by the required integrated light amount.
[0164] ◎: The accumulated light intensity is less than 500mJ / cm 2 The viscosity disappears.
[0165] ○: The integrated light intensity is 500mJ / cm 2 Above but less than 1000mJ / cm 2 The viscosity disappears.
[0166] Δ: The integrated light intensity is 1000mJ / cm 2 Above to less than 2000mJ / cm 2 The viscosity disappears.
[0167] ×: The integrated light intensity is 2000mJ / cm 2 The stickiness still remains when the above is applied.
[0168] [Table 1]
[0169]
[0170]
[0171] It is obvious from the results of Table 1 that the transparency and curability of the curable composition (D) containing non-water-soluble multifunctional (meth) acrylamide (A) and polymerizable compounds (B) other than A are excellent. Although A is non-water-soluble, it shows amphiphilicity and is therefore miscible with hydrophobic, hydrophilic and water-soluble B. In addition, when the SP value of A is 8.8 to 11.0, the SP value of B is 8.5 to 14.5, and the difference between the SP values of A and B is less than 3.0, the transparency of the obtained D is higher. It is known that by the total mass of D, the content of A is 1% to 95% by mass, the content of B is 5% to 99% by mass, and the content of monofunctional polymerizable compounds (b1) and / or multifunctional polymerizable compounds (b2) as B, the transparency and curability of D are good, especially if the total content of A and b2 exceeds 15% by mass, the curability of D becomes higher. On the other hand, when only A (Comparative Example 2) or only B (Comparative Example 4) is contained, the mutual solubility between A or B and the polymerization initiator is insufficient, so the transparency of the curable composition is poor. In addition, when no A (Comparative Example 4) is contained, water-soluble multifunctional (meth)acrylamide (Comparative Examples 1, 3 and 5), and water-insoluble multifunctional acrylate (Comparative Example 6) is contained, the transparency and curability of the curable composition are not satisfactory.
[0172] Examples 16 to 21 and Comparative Examples 7 and 8 (Preparation and Evaluation of Coating Compositions)
[0173] The curable composition, multifunctional (meth) acrylamide (A), polymerizable compound (B) and other components obtained in Table 1 were weighed according to the mass ratio shown in Table 2, mixed at 35°C for 1 hour, and the coating composition of Examples 16 to 21 and Comparative Examples 7 and 8 was modulated. The wettability of the obtained coating composition for various substrates and the resistance to curing shrinkage during active energy line curing were evaluated by the following method. In addition, a coating film (also referred to as a cured film or coating film) was prepared on a PET film using the coating composition by the following method, and the stickiness resistance, appearance and surface hardness of the obtained coating film were evaluated by the following method. The various evaluation results are shown in Table 2.
[0174] Evaluation of the wettability of coating compositions
[0175] The coating composition of each example and comparative example was applied to various substrates shown in Table 2 using a bar coater (No. 12), and the coating edge shrinkage of the coating liquid was visually observed.
[0176] ◎: There is no coating edge shrinkage and the coating film is uniform.
[0177] ○: Although there is very slight coating edge shrinkage, the coating film is substantially uniform.
[0178] Δ: There is some coating edge shrinkage, but the coating film is generally uniform overall.
[0179] ×: The coating film has much edge shrinkage and is uneven.
[0180] Evaluation of curing shrinkage resistance (curling resistance) of coating composition
[0181] The coating composition of each example and comparative example was applied to a PET film having a thickness of 100 μm using a bar coater (No. 12), and irradiated with ultraviolet light (device: variable flow conveyor device ECS-4011GX manufactured by EYE GRAPHICS, metal halide lamp: M04-L41 manufactured by EYE GRAPHICS, ultraviolet light intensity: 700 mW / cm 2 , integrated light quantity: 1000mJ / cm 2 ), thereby preparing a coating film with a film thickness of 10 μm. In addition, when a solvent is used, after coating, it is dried at 80°C for 3 minutes and then irradiated with ultraviolet rays. The obtained coating film is cut into 10 cm squares, and the average of the ridges at the four corners is measured to evaluate the resistance to curing shrinkage (curling resistance). The larger the ridge, the larger the curling, and the lower the resistance to curing shrinkage.
[0182] ◎: There are ridges of 0.5 mm or less.
[0183] ○: There is a bulge of 1 mm or less.
[0184] Δ: There is a bulge of 3 mm or less.
[0185] ×: Extremely curled.
[0186] Evaluation of the stickiness resistance of coating films
[0187] Using the coating composition of each embodiment and comparative example, a coating film was prepared using a rod coater (No. 6) so that the film thickness after drying was 5 μm and in the same manner as the above-mentioned evaluation of curing shrinkage resistance (curling resistance). The surface of the obtained coating film was contacted with a silicone rubber plug, and the stickiness (surface stickiness) was evaluated according to the following criteria. The results are shown in Table 1. The more severe the stickiness, the lower the stickiness resistance.
[0188] ◎: No stickiness at all.
[0189] ○: There is some stickiness, but no trace remains on the surface.
[0190] Δ: There is stickiness and traces remain on the surface.
[0191] ×: Severe stickiness, with the rubber plug sticking to the surface.
[0192] Evaluation of coating film appearance
[0193] Using the coating agent composition of each embodiment and comparative example, a coating film with a thickness of 10 μm was prepared in the same manner as the above-mentioned anti-curling property (anti-curling property) evaluation. The surface smoothness and transparency of the obtained coating film were visually observed, and the appearance of the coating film was evaluated according to the following benchmark. The higher the surface smoothness, the higher the transparency of the coating, and the better the appearance.
[0194] ◎: The surface is smooth and the coating film is transparent.
[0195] ○: The surface is smooth, and the coating film is transparent as a whole but has a slightly cloudy portion.
[0196] Δ: The surface is uneven or the coating film has a cloudy portion.
[0197] ×: The surface has irregularities and the coating film is turbid.
[0198] Evaluation of surface hardness of coating composition
[0199] Using the curable composition of each embodiment and comparative example, a coating film having a thickness of 10 μm was prepared in the same manner as the above-mentioned evaluation of curing shrinkage resistance (curling resistance). Using the obtained coating film, the surface hardness was evaluated as follows by scratching the film with a pencil at an angle of 45° for about 10 mm in accordance with JIS K 5600, and then setting the pencil hardness as the hardest pencil with no damage to the surface of the film.
[0200] ◎: Pencil hardness is 2H or more.
[0201] ○: Pencil hardness is HB to H.
[0202] Δ: Pencil hardness is 3B to B.
[0203] ×: Pencil hardness is 4B or less.
[0204] [Table 2]
[0205]
[0206] As can be clearly seen from the results of Table 2, the coating composition of the embodiment contains multifunctional (meth) acrylamide (A) and polymerizable compound (B), has high curability and resistance to curing shrinkage, and shows good wettability to various substrates such as plastic substrates (PET, PVC, ABS) to metals (aluminum). The coating film obtained by the coating composition of the embodiment has a good appearance, and the coating film has high stickiness and surface hardness. These effects are brought about by the interaction of A and B. The coating composition of the comparative example that does not contain A and B at the same time did not confirm the same characteristics.
[0207] Examples 22 to 27 and Comparative Examples 9 and 10 (Preparation and Evaluation of Adhesive Compositions)
[0208] The curable composition obtained in Table 1, the multifunctional (meth)acrylamide (A), the polymerizable compound (B), the photopolymerization initiator (C) and other components were weighed according to the mass ratio shown in Table 3, and mixed at 35°C for 1 hour to prepare the adhesive compositions of Examples 22 to 27 and Comparative Examples 9 and 10. The obtained adhesive compositions were used to prepare adhesive layers and adhesive sheets by the following method, and the curability of the adhesive compositions, the adhesion to various substrates, and the adhesive strength, transparency, stain resistance (secondary processing), yellowing resistance and moisture-heat resistance of the obtained adhesive layers were evaluated. The results are shown in Table 3.
[0209] Evaluation of curability of adhesive compositions
[0210] A heavy-peel PET film (manufactured by Toyobo Co., Ltd., polyester film E7001) with a thickness of 75 μm was placed in close contact with a horizontally arranged glass plate, and a spacer with a thickness of 1 mm and an inner area of 60 mm×100 mm was set. After the prepared curable adhesive composition of each embodiment and comparative example was filled inside the spacer, a light-peel PET film (manufactured by Toyobo Co., Ltd., polyester film E7002) with a thickness of 50 μm was overlapped on the composition. The light-peel PET film (manufactured by Toyobo Co., Ltd., polyester film E7002) with a wavelength of 385 nm and an output of 100 mW / cm 2 The UVLED lamp has an integrated light intensity of 3000mJ / cm 2 Then, the peeling PET films on both sides were removed, and the obtained cured product (adhesive layer) was touched with a finger and the curability was evaluated by dividing it into three levels according to the following criteria.
[0211] ○: A cured product that can maintain its shape is obtained. When the cured product is touched, stickiness is observed, but no liquid uncured material is attached.
[0212] Δ: A cured product that can maintain its shape is obtained. When the cured product is touched, stickiness is visible, but liquid uncured material is attached.
[0213] ×: The curing was insufficient and a cured product that could maintain its shape could not be obtained, and a large amount of liquid residue was observed to be attached.
[0214] Adhesive sheet preparation and adhesion evaluation
[0215] The adhesive composition of each embodiment and comparative example was applied to various plate-shaped substrates (substrates), and the film was laminated using a table-top roll laminator (RSL-382S manufactured by Royal Sovereign) in a manner that the release film (silicone-coated PET film) was lightly peeled off without entraining bubbles, so that the adhesive layer had a thickness of 5 μm, and irradiated with ultraviolet light (device: variable flow conveyor device ECS-4011GX manufactured by EYE GRAPHICS, metal halide lamp: M04-L41 manufactured by EYE GRAPHICS, ultraviolet light irradiance: 700 mW / cm 2 , integrated light quantity: 5000mJ / cm 2 ). Then, the light peeling release film was peeled off to obtain an adhesive sheet consisting of an adhesive layer and a substrate. Using the obtained adhesive sheet, 100 1 mm square grids were made according to JIS K 5600, and transparent tape was attached. The number of grids with the adhesive layer remaining on the substrate side when peeled off at one go was counted, and the adhesion was evaluated according to the following criteria. The more the number of remaining grids, the higher the adhesion.
[0216] ◎: The number of remaining grids is 100.
[0217] ○: The number of remaining grids is 95 to 99.
[0218] Δ: The number of remaining grids is 70 to 94.
[0219] ×: The number of remaining grids is 0 to 69.
[0220] Adhesion evaluation
[0221] Under the conditions of temperature 23°C and relative humidity 50%, the above adhesive layer was transferred to various film-shaped or plate-shaped substrates, and a 2kg pressure roller was used to press and attach the substrates twice, and the substrates were placed in the same atmosphere for 30 minutes. Then, a tensile tester (device name: Tensilon RTA-100 manufactured by O RIENTEC) was used to measure the 180° peel strength (N / 25mm) at a peel speed of 300mm / min according to JIS Z0237. The higher the peel strength, the higher the adhesive force.
[0222] ◎: 30 (N / 25mm) or more.
[0223] ○: 15 (N / 25 mm) or more and less than 30 (N / 25 mm).
[0224] Δ: 8 (N / 25mm) or more and less than 15 (N / 25mm).
[0225] ×: less than 8 (N / 25 mm).
[0226] Evaluation of transparency of adhesive layer
[0227] The total light transmittance of the glass substrate was measured using a haze meter (manufactured by Nippon Denshoku Industries, NDH-2000) in accordance with JIS K 7105. The adhesive layer was transferred to the glass substrate at a temperature of 23°C and a relative humidity of 50%, and the total light transmittance of the glass substrate and the adhesive layer was measured. Then, the transmittance of the glass plate was subtracted to calculate the transmittance of the adhesive layer itself, and the transparency was evaluated in 4 levels as described below. The higher the transmittance, the higher the transparency.
[0228] ◎: The transmittance is 90% or more.
[0229] ○: The transmittance is 85% or more and less than 90%.
[0230] Δ: The transmittance is 50% or more and less than 85%.
[0231] ×: The transmittance is less than 50%.
[0232] Evaluation of the stain resistance (secondary processing properties) of the adhesive layer
[0233] An adhesive sheet was prepared in the same manner as above and left at 80°C for 24 hours. After peeling off the adhesive layer, the contamination on the surface of the substrate film (the residual state of the adhesive layer (paste)) was visually observed. The less the residual paste, the higher the contamination resistance.
[0234] ◎: No pollution (no paste residue).
[0235] ○: Contamination is very slightly present.
[0236] Δ: Slight contamination exists.
[0237] ×: Contamination is present (paste residue is present).
[0238] Evaluation of yellowing resistance of adhesive layer
[0239] An adhesive sheet was prepared in the same manner as above and placed in a xenon attenuator (SC-700-WA: manufactured by Suga Test Instruments) at 70 mW / cm 2 After irradiation with ultraviolet rays of an intensity of 1000 nm for 120 hours, the discoloration of the adhesive layer on the adhesive sheet was visually observed.
[0240] ◎: No yellowing was observed visually.
[0241] ○: Yellowing was very slightly observed visually.
[0242] Δ: Yellowing was observed visually.
[0243] ×: Clear yellowing was observed visually.
[0244] Evaluation of moisture and heat resistance of adhesive layer
[0245] An adhesive sheet was prepared in the same manner as above, and after being kept at a temperature of 85° C. and a relative humidity of 85% for 100 hours, the adhesive layer was visually observed for the presence or absence of bulges, peeling, bubbles, or white turbidity, and evaluated.
[0246] ◎: Transparent, with no swelling, peeling or bubbles.
[0247] ○: There was very slight blurring, but no swelling, peeling, or bubbles occurred.
[0248] Δ: Slight blurring, swelling, peeling, or bubbles are present.
[0249] ×: Severe blurring, swelling, peeling, or bubbles are present.
[0250] [Table 3]
[0251]
[0252]
[0253] It is obvious from the results of Table 3 that the adhesive composition of the embodiment contains multifunctional (meth) acrylamide (A) and polymerizable compound (B). Through the interaction of these components, the adhesive composition shows high curability, and the transparency of the adhesive layer obtained by curing the adhesive composition is high. In addition, the adhesive composition of the embodiment has good adhesion and adhesion (adhesion) for various materials from general plastics to inorganic glass. The cured product (adhesive layer) obtained by the adhesive composition of the embodiment maintains high transparency, and the contamination resistance of the cured product when peeled off from the substrate and the yellowing resistance and moisture and heat resistance of the cured product are all good. On the other hand, it can be seen that in the composition of the comparative example, the curability, the adhesion and adhesion to various materials are all low, and the transparency, contamination resistance, yellowing resistance and moisture and heat resistance of the cured product are all low.
[0254] Examples 28 to 33 and Comparative Examples 11 and 12 (Preparation and Evaluation of Adhesive Compositions)
[0255] The curable composition obtained in Table 1, the multifunctional (meth)acrylamide (A), the polymerizable compound (B), the photopolymerization initiator (C) and other components were weighed according to the mass ratio shown in Table 4, and mixed at 35°C for 1 hour to prepare the adhesive compositions of Examples 28 to 33 and Comparative Examples 11 and 12. The transparency of the obtained adhesive compositions was evaluated by the following method. In addition, the adhesive compositions of each Example and Comparative Example were used to bond the same or different plate-like substrates by the following method to prepare adhesive test pieces, and the adhesion, water resistance and impact resistance were evaluated. The results are shown in Table 4.
[0256] Evaluation of transparency of adhesive compositions
[0257] The obtained adhesive composition was left to stand at 23° C. overnight, and the state was visually observed, and the transparency was evaluated by being classified into four levels as follows.
[0258] ⊚: High transparency, and no turbidity or separation was observed.
[0259] ○: High transparency, but slightly turbid.
[0260] Δ: Layer separation did not occur, but white turbidity occurred.
[0261] ×: White turbidity occurred, and further layer separation occurred.
[0262] Preparation of Adhesive Test Pieces
[0263] Use two plates of the same or different types of substrates with a length of 100 mm × a width of 25 mm × a thickness of 1 mm, and evenly apply the adhesive composition on any one of them. In addition, when the adhesive composition contains a solvent, apply a slightly larger amount of the mixture so that the thickness after drying is the same as that without a solvent, and dry it at 90°C for two minutes. Then, according to JIS K 6850, place another plate-shaped substrate on the applied adhesive composition, and bond them so that the overlapping area becomes 12.5 mm × 25 mm in length, and adjust the thickness of the adhesive layer to 100 μm by using a spacer to prepare a bonded test piece. Then, ultraviolet light is applied from the upper surface of the bonded transparent or translucent substrate (ultraviolet light irradiation device: variable flow conveyor device ECS-4011GX manufactured by EYE GRAPHICS, metal halide lamp: M04-L41 manufactured by EYE GRAPHICS, ultraviolet light illumination: 700 mW / cm 2 , integrated light quantity: 5000mJ / cm 2 The irradiated test piece was used as an adhesive test piece.
[0264] Adhesion evaluation
[0265] The obtained adhesive test piece was used to measure the tensile shear strength at a tensile speed of 10 mm / min using Tensilon RTA-100 (manufactured by ORIENTEC) as a testing machine in accordance with JIS K 6850. The higher the tensile shear strength, the higher the adhesive force.
[0266] ◎: Tensile shear strength is 20 MPa or more.
[0267] ○: The tensile shear strength is 15 MPa or more and less than 20 MPa.
[0268] Δ: The tensile shear strength is 10 MPa or more and less than 15 MPa.
[0269] ×: The tensile shear strength was less than 10 MPa.
[0270] Water resistance of adhesive test piece
[0271] The obtained adhesive test piece was immersed in warm water at 60° C. for 48 hours, and then the presence or absence of peeling at the interface between the same or different plate-like substrates was confirmed and evaluated based on the following criteria.
[0272] ◎: No peeling at the interface (less than 1 mm).
[0273] ○: There is peeling at a part of the interface (1 mm or more and less than 3 mm).
[0274] Δ: There is peeling at a part of the interface (3 mm or more and less than 5 mm).
[0275] ×: There is peeling at the interface (5 mm or more).
[0276] Evaluation of impact resistance of adhesive test pieces
[0277] The obtained adhesive test piece was used to measure the impact peel strength using an impact tester No. 511 (manufactured by MYS-TESTER) in accordance with JIS K6855. The higher the impact peel strength, the higher the impact resistance.
[0278] ◎: Impact peel strength is 20KJ / m 2 above.
[0279] ○: Impact peel strength is 15KJ / m 2 Above but less than 20KJ / m 2 .
[0280] Δ: Impact peel strength is 10KJ / m 2 Above but less than 15KJ / m 2 .
[0281] ×: Impact peel strength is less than 10KJ / m 2 .
[0282] [Table 4]
[0283]
[0284] It is obvious from the results of Table 4 that the adhesive composition of the embodiment contains multifunctional (meth) acrylamide (A) and polymerizable compound (B), showing high transparency. In addition, the adhesive composition of the embodiment is used for the adhesion of various materials of the same or different species, such as plastic substrates (PET, PMMA, PC, PVC, ABS) to metals (aluminum), and a sufficiently satisfactory adhesion is obtained. The reason is that the adhesive composition has excellent wettability for various materials, and the adhesive obtained after curing has high adhesion. In addition, by having A containing multiple isopropyloxy groups, the water resistance and impact resistance of the adhesive obtained in the embodiment are both good, especially in Examples 29 to 31 where isopropyloxy groups with branched structures are introduced, it is confirmed that the water resistance and impact resistance are further improved. On the other hand, the adhesive composition of the comparative example that does not contain A and B at the same time and the adhesive obtained from these compositions did not confirm the same characteristics.
[0285] Examples 34 to 39 and Comparative Examples 13 and 14 (Preparation and Evaluation of Curable Ink Compositions)
[0286] The curable composition obtained in Table 1, the multifunctional (meth)acrylamide (A), the polymerizable compound (B), the photopolymerization initiator (C) and other components were weighed according to the mass ratio shown in Table 5, and mixed at 35°C for 1 hour to prepare the ink compositions of Examples 34 to 39 and Comparative Examples 13 and 14. The obtained ink compositions were used to measure the viscosity by the following method, and the transparency of the case without pigment (transparent ink) and the pigment dispersibility of the case containing pigment were evaluated. In addition, the curability of the ink composition and the discharge stability during inkjet printing were evaluated, and the clarity of the obtained printed matter was evaluated. The evaluation results are summarized in Table 5.
[0287] Viscosity measurement and evaluation of ink compositions
[0288] The viscosity of the obtained ink composition at 25° C. was measured using a cone and plate viscometer (RE550 viscometer manufactured by Toki Sangyo Co., Ltd.) in accordance with JIS K5600-2-3. The viscosity of the ink composition for inkjet printing was evaluated in four grades as follows.
[0289] ◎: 5 mPa·s or more and less than 100 mPa·s.
[0290] ○: 100 mPa·s or more and less than 500 mPa·s.
[0291] Δ: 500 mPa·s or more and less than 2000 mPa·s.
[0292] ×: 2000 mPa·s or more.
[0293] Pigment dispersion evaluation
[0294] The obtained ink composition was used to visually observe the aggregation or precipitation state of the pigment immediately after preparation and after being left to stand at room temperature for two months, and the pigment dispersibility was evaluated according to the following criteria.
[0295] ◎: No aggregation or precipitation of the pigment was observed immediately after preparation and after standing for two months.
[0296] ○: Pigment aggregation or precipitation was not observed at all immediately after preparation, but was slightly observed after being left to stand for two months.
[0297] Δ: Aggregation or precipitation of the pigment was slightly observed immediately after preparation, or aggregation or precipitation of the pigment was clearly observed after being left to stand for two months.
[0298] ×: Aggregation or precipitation of the pigment was clearly observed immediately after preparation.
[0299] Transparency evaluation (transparent ink)
[0300] The obtained ink composition was placed in a transparent spiral tube, the initial state was visually observed, and the ink composition was left standing at room temperature in a dark place for 24 hours. The state of the ink composition after standing was then visually observed, and the miscibility was evaluated according to the following criteria.
[0301] ◎: No separation of the liquid layers or turbidity was observed both initially and after standing.
[0302] ○: No layer separation or white turbidity of the liquid was observed initially, but layer separation or white turbidity was slightly observed after standing.
[0303] Δ: Layer separation or white turbidity was slightly observed initially, but layer separation or white turbidity was clearly observed after standing.
[0304] ×: Clear layer separation or white turbidity was observed even at the beginning.
[0305] Production of printed matter using active energy ray irradiation
[0306] The ink composition was applied to a PET film having a thickness of 100 μm using a bar coater (No. 12) (film thickness after drying: 10 μm), and irradiated with ultraviolet light (device: variable flow conveyor device ECS-4011GX manufactured by EYE GRAPHICS, metal halide lamp: M04-L41 manufactured by EYE GRAPHICS, ultraviolet light intensity: 700 mW / cm 2 , integrated light quantity: 1000mJ / cm 2 ), thereby solidifying it and making printed matter.
[0307] Evaluation of curability of ink composition
[0308] Printed materials were prepared by the above method, and the integrated light intensity required until the ink composition was completely cured (not sticky) was measured to evaluate the curability. The lower the required integrated light intensity, the higher the curability.
[0309] ◎: Less than 1000mJ / cm 2 When fully cured.
[0310] ○: 1000 or more but less than 2000 mJ / cm 2 When fully cured.
[0311] Δ: 2000 or more but less than 5000 mJ / cm 2 When fully cured.
[0312] ×: 5000 mJ / cm is required for complete curing 2 above.
[0313] Inkjet printing and ink discharge stability evaluation
[0314] The ink composition was filled in a commercially available inkjet printer (LuxelJet UV350GTW manufactured by Fujifilm Corporation), and a solid image was printed using coated paper. The printing state of the obtained printed matter was visually observed, and the discharge stability was evaluated according to the following criteria.
[0315] ◎: Good printing without any leakage.
[0316] ○: There is slight leakage.
[0317] Δ: There is leakage in a wide range.
[0318] ×: Existed but not discharged.
[0319] Clarity evaluation
[0320] The image clarity of the printed matter obtained by ink jet printing using the ink composition containing the pigment was visually observed.
[0321] ◎: No ink bleeding was observed and the image was clear.
[0322] ○: There is almost no ink bleeding and the image is good.
[0323] Δ: Some ink bleeding is visible.
[0324] ×: Remarkable ink bleeding is observed.
[0325] [Table 5]
[0326]
[0327] As can be clearly seen from the results in Table 5, the ink composition of the embodiment contains a multifunctional (meth)acrylamide (A) and a polymerizable compound (B) with high mutual solubility, and has high transparency (transparent ink) or pigment dispersibility. In addition, the ink composition containing A and B has high curability, and as an ink composition for inkjet printing, the viscosity can be adjusted to a low level, and the discharge stability and the print clarity of the obtained printed matter are both good. On the other hand, the viscosity, transparency, pigment dispersibility, curability or discharge stability of the ink composition of the comparative example are all low, and the print clarity of the obtained printed matter is not satisfactory.
[0328] Examples 40 to 45 and Comparative Examples 15 and 16 (Preparation and Evaluation of Aqueous Ink Compositions)
[0329] The curable composition obtained in Table 1, the multifunctional (meth)acrylamide (A), the polymerizable compound (B), the photopolymerization initiator (C), water and other components were weighed according to the mass ratio shown in Table 6, and mixed at 35°C for 1 hour to prepare the aqueous ink compositions of Examples 40 to 45 and Comparative Examples 15 and 16. The obtained aqueous ink compositions were used to evaluate the miscibility with water (transparent ink) and the dispersibility of water-soluble pigments by the following method. In addition, the initial viscosity was measured to evaluate the viscosity suitability as an ink composition for inkjet printing. Furthermore, the obtained aqueous ink composition was stored in a dark place at 40°C for one month, and the viscosity was measured in the same manner after storage. The change rate of the viscosity after storage relative to the initial value was calculated by the following formula, and the storage stability of the ink was evaluated according to the following criteria. The curability of the aqueous ink composition and the discharge stability during inkjet printing were evaluated, and the surface dryness and clarity of the obtained printed matter were evaluated. The evaluation results are summarized in Table 6.
[0330] Viscosity change rate (%) = (viscosity after storage - initial viscosity) / initial viscosity × 100%
[0331] Mutual solubility evaluation (transparent ink)
[0332] The obtained aqueous ink composition was placed in a transparent spiral tube, the initial state was visually observed, and the composition was left standing in a dark place at room temperature for 24 hours. The state of the aqueous ink composition after standing was then visually observed, and the miscibility was evaluated according to the following criteria.
[0333] ◎: No separation of the liquid layers or turbidity was observed both initially and after standing.
[0334] ○: No layer separation or white turbidity of the liquid was observed initially, but layer separation or white turbidity was slightly observed after standing.
[0335] Δ: Layer separation or white turbidity was slightly observed initially, but layer separation or white turbidity was clearly observed after standing.
[0336] ×: Clear layer separation or white turbidity was observed even at the beginning.
[0337] Evaluation of pigment dispersibility of aqueous ink compositions
[0338] The obtained aqueous ink composition containing aqueous pigment was placed in a transparent spiral tube, the initial state was observed visually, and the mixture was left standing at room temperature in a dark place for 24 hours. Then, the state of the aqueous ink composition containing aqueous pigment after standing was observed visually, and the pigment dispersibility was evaluated according to the following criteria.
[0339] ◎: No precipitation of the pigment was observed at all both initially and after standing.
[0340] ○: No precipitation of the pigment was observed initially, but precipitation of the pigment was slightly observed after standing.
[0341] Δ: Pigment precipitation is slightly observed initially, but obvious pigment precipitation is observed after standing.
[0342] ×: Initially, obvious precipitation of the pigment was also observed.
[0343] Determination and evaluation of viscosity of aqueous ink compositions
[0344] The viscosity of the obtained aqueous ink composition was measured using a cone and plate viscometer (RE550 viscometer manufactured by Toki Sangyo Co., Ltd.) in accordance with JIS K5600-2-3. The viscosity suitability of the ink composition for inkjet printing was evaluated based on the following criteria.
[0345] ◎: 5 mPa·s or more and less than 100 mPa·s.
[0346] ○: 100 mPa·s or more and less than 500 mPa·s.
[0347] Δ: 500 mPa·s or more and less than 2000 mPa·s.
[0348] ×: 2000 mPa·s or more.
[0349] Evaluation of storage stability of aqueous ink compositions
[0350] Similarly, the viscosity of the aqueous ink composition after storage at 40° C. in a dark place for one month was measured, and the viscosity change rate was calculated and evaluated according to the following criteria.
[0351] ◎: The rate of change is less than ±10%.
[0352] ○: The variation rate is from ±10% or more to less than ±20%.
[0353] Δ: The variation rate is more than ±20% and less than ±30%.
[0354] ×: The variation rate is ±30% or more.
[0355] Production and evaluation of printed matter using water-based ink compositions
[0356] The obtained aqueous ink composition was used to print on OK coated paper (manufactured by Oji Paper) using an inkjet evaluation device (manufactured by K-SOLUTION Co., Ltd.), and the integrated light intensity (200 mJ / cm 2 ) was irradiated with ultraviolet light to cure the ink to obtain a printed matter. The discharge stability of the aqueous ink composition, the surface drying property and water resistance of the obtained printed matter were evaluated according to the following criteria.
[0357] Evaluation of discharge stability of aqueous ink composition
[0358] The printing state of the obtained printed matter was evaluated by visual observation.
[0359] ◎: Good printing without any leakage.
[0360] ○: There is slight leakage.
[0361] Δ: There is leakage in a wide range.
[0362] ×: Existed but not discharged.
[0363] Evaluation of curability of aqueous ink compositions
[0364] The obtained printed matter was rubbed with a cotton swab, and the curability was evaluated according to the following criteria.
[0365] ◎: No trace of rubbing with a cotton swab remains.
[0366] ○: Slight traces of friction remain.
[0367] Δ: Traces of friction remain over a wide area.
[0368] ×: The printed material was obtained using a cotton swab.
[0369] Evaluation of surface dryness of printed materials
[0370] The obtained printed material was left to stand for five minutes in an environment with a room temperature of 23°C and a relative humidity of 50%. A woodfree paper was overlapped on the printed surface and a load of 1 kg / cm was applied. 2 The degree of ink transfer to paper was evaluated by holding the load for one minute.
[0371] ◎: The ink is dry and there is no transfer to the paper.
[0372] ○: The ink was dry, but slightly transferred to paper.
[0373] Δ: The ink is almost dry and has been transferred to the paper.
[0374] ×: The ink was hardly dried and much ink was transferred to the paper.
[0375] Evaluation of water resistance of aqueous ink compositions
[0376] The obtained printed matter was rubbed with a cotton swab moistened with water, and the water resistance was evaluated according to the following criteria.
[0377] ◎: No ink components adhered to the cotton swab and no traces of friction on the printed surface were observed even after 40 reciprocating strokes.
[0378] ○: When the cotton swab was moved back and forth 40 times, there were slight traces of ink components adhering to the cotton swab and friction marks on the printed surface.
[0379] Δ: Adhesion of ink components to the cotton swab and traces of friction on the printed surface were found from 11 to 39 times of reciprocation.
[0380] ×: Ink components adhere to the cotton swab and there are traces of friction on the printed surface when the cotton swab is used for less than 10 reciprocating strokes.
[0381] [Table 6]
[0382]
[0383]
[0384] It is obvious from the results of Table 6 that the water-based ink composition of the embodiment is low in viscosity, has high mutual solubility or pigment dispersibility, and has good discharge stability in inkjet printing. In addition, the water-based ink composition of the embodiment has good storage stability and high curability. The reason for obtaining such a result is that the water-based ink composition of the embodiment contains non-water-soluble multifunctional (methyl) acrylamide (A) and polymerizable compound (B), A and B have extremely high mutual solubility, and pigment dispersibility and water solubility are both excellent. It can be confirmed that the printed matter obtained by curing the water-based ink composition of the embodiment has excellent surface dryness and printing clarity. On the other hand, in the water-based ink composition of the comparative example and the printed matter of these water-based ink compositions, the characteristic evaluation of multiple items is not satisfactory.
[0385] Examples 46 to 51 and Comparative Examples 17 and 18 (Preparation and Evaluation of Ink Compositions for Three-Dimensional Modeling)
[0386] The curable composition obtained in Table 1, the multifunctional (meth)acrylamide (A), the polymerizable compound (B), the photopolymerization initiator (C) and other components were weighed in the mass ratio shown in Table 7, and mixed at 35°C for one hour to prepare the three-dimensional modeling ink compositions of Examples 46 to 51 and Comparative Examples 17 and 18. Using the obtained three-dimensional modeling ink compositions, three-dimensional objects were prepared by the following method, and the curing shrinkage resistance of the three-dimensional modeling ink compositions, the strength, impact resistance, water resistance and modeling accuracy of the obtained cured products were evaluated. The evaluation results are shown in Table 7.
[0387] Fabrication and strength evaluation of three-dimensional structures
[0388] A heavy release PET film (produced by Toyobo Co., Ltd., polyester film E7001) with a thickness of 75 μm was placed in close contact with a horizontally placed glass plate, and a spacer with a thickness of 1 mm and an interior punched into a dumbbell shape No. 2 in accordance with JIS K6251 was provided. After the three-dimensional modeling ink composition obtained in each example and comparative example was filled inside the spacer, a light release PET film (produced by Toyobo Co., Ltd., polyester film E7002) with a thickness of 50 μm was stacked on the composition, and ultraviolet rays were irradiated from both sides (device: variable flow conveyor device ECS-4011GX manufactured by EYE GRAPHICS, metal halide lamp: M04-L41 manufactured by EYEGRAPHICS, ultraviolet irradiance 200 mW / cm2, integrated light quantity 1000 mJ / cm 2) to cure the ink composition for three-dimensional modeling. Then, the peeling PET films on both sides were removed to obtain a test piece of the cured product for strength evaluation. According to JIS K7161, a table-top precision universal testing machine (Autograph AGS-X manufactured by Shimadzu Corporation) was used to measure the tensile strength at a temperature of 25°C, at a tensile speed of 10 mm / min and a distance between chucks of 50 mm, and the strength was evaluated according to the following criteria.
[0389] ◎: The tensile strength is 40 MPa or more.
[0390] ○: The tensile strength is 30 MPa or more and less than 40 MPa.
[0391] Δ: The tensile strength is 20 MPa or more and less than 30 MPa.
[0392] ×: The tensile strength was less than 20 MPa.
[0393] Evaluation of the curing shrinkage resistance of ink compositions for three-dimensional modeling
[0394] The cured product was prepared in the same manner as the test piece for the strength evaluation described above, and the cure shrinkage ratio was calculated from the specific gravity (d0) of the curable composition before curing and the specific gravity (d1) of the sheet-like cured product obtained after curing according to JIS K5600 2-4, and the cure shrinkage resistance was evaluated based on the following criteria. The lower the cure shrinkage ratio, the higher the cure shrinkage resistance.
[0395] Curing shrinkage (%) = (d1-d0) / d1×100%
[0396] ◎: Less than 2%.
[0397] ○: 2% to less than 5%.
[0398] Δ: 5% to less than 10%.
[0399] ×: 10% or more.
[0400] Evaluation of impact resistance (toughness) of three-dimensional structures
[0401] In the same manner as the test piece for strength evaluation described above, a spacer with a thickness of 4 mm and an inner area of 10 mm × 80 mm was prepared, and the three-dimensional shaping ink composition obtained in each embodiment and comparative example with a thickness of 4 mm was filled inside the spacer, and a light peeling PET film was overlapped in the same manner, and ultraviolet rays were irradiated from both sides to cure the ink composition. Then, the peeling PET films on both sides were removed, and ultraviolet rays were irradiated at a predetermined integrated light amount (device: manufactured by Aitec System Co., Ltd., desktop batch type UV-LED curing device MUVBA-0.3×0.3×0.5, wavelength 405nm, illumination (UV-V) 50mW / cm 2 , total light intensity 5,000mJ / cm 2 ), post-curing treatment was performed to completely cure it. Then, the obtained cured product was used as a test piece, and the Izod impact strength (with notch) was measured according to JIS K-7110, and the impact resistance was evaluated as follows. In addition, the Izod-Charpy impact tester "Model No. 195-R" manufactured by Yasuda Seiki Manufacturing Co., Ltd. was used. The higher the impact strength, the higher the impact resistance.
[0402] ◎: 40J / m or more.
[0403] ○: 30 J / m or more and less than 40 J / m.
[0404] Δ: 20 J / m or more and less than 30 J / m.
[0405] ×: less than 20 J / m.
[0406] Evaluation of water resistance of three-dimensional structures
[0407] Use a spacer with a thickness of 1mm and an interior of 10cm×1cm to make a cured test piece for water resistance evaluation with a length of 10cm×width of 1cm×thickness of 1mm in the same way as the test piece for strength evaluation mentioned above. After measuring the weight of the obtained test piece just after forming, immerse it in a beaker filled with 100ml of water, and measure the weight after immersion one day later. The water absorption rate is calculated by the following formula based on the weight before immersion and the weight after immersion, and the water resistance is evaluated according to the following criteria. The lower the water absorption rate, the higher the water resistance.
[0408] Water absorption (%) = (weight after immersion - weight before immersion) / weight before immersion × 100%
[0409] ◎: Water absorption rate is less than 2%.
[0410] ○: The water absorption rate is 2% or more and less than 2.5%.
[0411] Δ: The water absorption rate is 2.5% or more and less than 3%.
[0412] ×: The water absorption rate is 3% or more.
[0413] Modeling accuracy evaluation
[0414] In the same manner as the test piece for strength evaluation described above, a spacer with a thickness of 10 mm and an interior of 10 mm×10 mm was prepared. After the inner side of the spacer was filled with the ink composition for three-dimensional modeling obtained in each embodiment and comparative example with a thickness of 1 mm, the surface was smoothed by keeping at 60°C for 30 seconds, and then irradiated with ultraviolet light in the same manner to cure the ink composition for three-dimensional modeling. Then, the ink composition for three-dimensional modeling was filled with a thickness of 1 mm on the obtained cured product, and the curing was repeated a total of 10 times to obtain a cured product of 10 mm×10 mm×10 mm. The height of the obtained cured product was measured, and the side surface was visually observed, and the shaping accuracy was evaluated according to the following criteria.
[0415] ◎: The height is less than ±0.1mm for 10mm and there are no irregularities on the side.
[0416] ○: Height is 10 mm ± 0.1 mm or more and less than ± 0.2 mm, or there are slight irregularities on the side surface.
[0417] Δ: Height is 10 mm ± 0.2 mm or more but less than ± 0.3 mm, or there are slight irregularities on the side.
[0418] ×: The height is 10 mm ± 0.3 mm or more, or there are obvious irregularities on the side.
[0419] [Table 7]
[0420]
[0421]
[0422] As can be clearly seen from the results of Table 7, the ink composition for three-dimensional modeling in the examples contains water-insoluble multifunctional (meth)acrylamide (A) and polymerizable compound (B), and the obtained products have good strength, impact resistance, water resistance and modeling accuracy. In particular, in Examples 49 and 51 containing A having a branched isopropyloxy group, it was confirmed that the curing shrinkage resistance of the ink composition for three-dimensional modeling and the water resistance and impact resistance of the obtained products were further improved. On the other hand, in the comparative examples that did not contain both A and B, the curing shrinkage resistance of the ink composition for three-dimensional modeling was low, and the various physical properties of the obtained products were also low.
[0423] Examples 52 to 57 and Comparative Examples 19 and 20 (Preparation and Evaluation of Water-Based Coating Compositions)
[0424] The curable composition, multifunctional (meth)acrylamide (A), polymerizable compound (B), photopolymerization initiator (C) and other components obtained in Table 1 were weighed according to the mass ratio shown in Table 8, and mixed at 35°C for one hour to prepare the water-based coating compositions of Examples 52 to 57 and Comparative Examples 19 and 20. The obtained water-based coating composition was applied on an ABS substrate using a rod coater (No. 12) (film thickness 10 μm after drying), and dried at 80°C for 10 minutes using a hot air dryer. Then, the mixture was irradiated with ultraviolet light (the same variable flow conveyor device manufactured by EYE GRAPHICS as above, the same metal halide lamp as above, ultraviolet light intensity: 300 mW / cm 2 , total light quantity 2000mJ / cm 2 ), the dried coating films obtained in Examples 52 to 56 and Comparative Examples 19 and 20 were cured to obtain UV cured solids (cured coating films). In addition, the dried coating film obtained in Example 57 was heat-cured for 10 minutes using a hot air dryer at 120°C to obtain a heat-cured solid (cured coating film). The appearance, adhesion, warm water resistance, and chemical resistance of the obtained solids were evaluated using the following methods, and the results are shown in Table 8.
[0425] Appearance evaluation of cured film of waterborne coatings
[0426] The obtained cured coating film was visually observed, and the appearance was evaluated based on the following criteria based on the surface smoothness and transparency of the cured coating film.
[0427] Coating appearance:
[0428] ◎: The surface is smooth and the coating film is transparent.
[0429] ○: The surface is smooth, and the coating film is transparent as a whole with a slightly cloudy portion.
[0430] Δ: The surface is uneven or the coating film has a cloudy portion.
[0431] ×: The surface has irregularities and the coating film is turbid.
[0432] Evaluation of adhesion of cured film of waterborne coating
[0433] According to JIS K 5600, 100 1 mm square grids were made on the cured coating film, an adhesive tape was attached, and the number of grids of the cured film remaining on the substrate side when peeled off at once was counted to evaluate the adhesion according to the following criteria. The more grids that remained, the higher the adhesion.
[0434] ◎: The number of remaining grids is 100.
[0435] ○: The number of remaining grids is 90 or more and less than 100.
[0436] Δ: The number of remaining grids is 50 or more and less than 90.
[0437] ×: The number of remaining grids is less than 50.
[0438] Evaluation of hot water resistance of cured waterborne coatings
[0439] The obtained cured film on the ABS substrate was immersed in 80°C warm water for two hours together with the ABS plate, and then taken out and dried at 25°C for two hours. Then, the above-mentioned adhesion evaluation was performed, the number of remaining grids was counted, and the warm water resistance was evaluated according to the following criteria. The more the number of remaining grids, the higher the warm water resistance.
[0440] ◎: The number of remaining grids is 100.
[0441] ○: The number of remaining grids is 90 or more and less than 100.
[0442] Δ: The number of remaining grids is 50 or more and less than 90.
[0443] ×: The number of remaining grids is less than 50.
[0444] Evaluation of Chemical Resistance of Cured Films of Waterborne Coatings
[0445] The obtained cured film on the ABS substrate was immersed in a pH 9 NaOH aqueous solution at 60°C for one hour together with the ABS plate, and then taken out and dried at 25°C for two hours. Then, the above-mentioned adhesion evaluation was performed, the number of remaining grids was counted, and the chemical resistance was evaluated according to the following criteria. The greater the number of remaining grids, the higher the chemical resistance.
[0446] ◎: The number of remaining grids is 100.
[0447] ○: The number of remaining grids is 90 or more and less than 100.
[0448] Δ: The number of remaining grids is 50 or more and less than 90.
[0449] ×: The number of remaining grids is less than 50.
[0450] [Table 8]
[0451]
[0452] As can be clearly seen from the results of Table 8, the water-based coating composition of the embodiment has high adhesion, can be cured by UV (active energy line) and heat, and can obtain a cured film with high transparency and high surface smoothness, i.e. excellent appearance. In addition, the warm water resistance and chemical resistance of the cured film obtained are all good. These properties are the result that the water-based coating composition of the embodiment as described above contains non-aqueous multifunctional (methyl) acrylamide (A) and polymerizable compound (B) simultaneously. On the other hand, the water-based coating composition of the comparative example does not contain A and B simultaneously, so the physical property of the cured film cannot be satisfactory.
[0453] Examples 58 to 62 and Comparative Examples 21 and 22 (Preparation and Evaluation of Sealant Compositions)
[0454] The curable composition obtained in Table 1, the multifunctional (meth)acrylamide (A), the polymerizable compound (B), the photopolymerization initiator (C) and other components were weighed in the mass ratio shown in Table 9, and mixed at 35° C. for one hour to prepare the sealant compositions of Examples 58 to 62 and Comparative Examples 21 and 22. Using the obtained sealant compositions, sealant cured products (sealant layers) were prepared by the following method, and the physical properties of the obtained sealant layers were evaluated as follows.
[0455] Preparation of sealant cured product (sealing layer)
[0456] A silicone spacer (30 mm long x 15 mm wide x 3 mm thick) was placed on a glass plate (50 mm long x 50 mm wide x 5 mm thick), a copper foil (5 mm long x 5 mm wide x 80 μm thick) was placed inside the spacer, and the prepared curable sealant composition was injected. After sufficient degassing, ultraviolet rays were irradiated (the same variable flow conveyor device manufactured by EYE GRAPHICS as above, the same metal halide lamp as above, ultraviolet irradiance: 700 mW / cm 2 , integrated light quantity: 1000mJ / cm 2 ) to obtain a sealant cured product. The properties of the obtained cured product were evaluated by the following methods, and the results are shown in Table 9.
[0457] Transparency evaluation of cured sealants
[0458] The portion without copper foil was cut from the obtained sealant cured product, and after standing for 24 hours in an atmosphere of temperature 23°C and relative humidity 50%, the transmittance of the cured product was measured by a haze meter (NDH-2000 manufactured by Nippon Denshoku Industries Co., Ltd.), and the transparency was evaluated according to the following criteria. The higher the transmittance, the higher the transparency.
[0459] ◎: The transmittance is 90% or more.
[0460] ○: The transmittance is 85% or more and less than 90%.
[0461] Δ: The transmittance is 50% or more and less than 85%.
[0462] ×: The transmittance is less than 50%.
[0463] Evaluation of water resistance of cured sealants
[0464] 1 g of the obtained solidified product was cut out and placed in a constant temperature and humidity chamber at 85°C and 95% as a test piece. After standing for 48 hours, the weight of the test piece was measured again, and the water absorption was calculated by the following formula. The water resistance was evaluated by the following criteria. The lower the water absorption, the higher the water resistance.
[0465] Water absorption rate (%) = (weight after water absorption - weight before water absorption) / weight before water absorption × 100%
[0466] ◎: Water absorption rate is less than 1.0%.
[0467] ○: The water absorption rate is 1.0% or more and less than 2.0%.
[0468] Δ: The water absorption rate is 2.0% or more and less than 3.0%.
[0469] ×: The water absorption rate is 3.0% or more.
[0470] Outgassing resistance evaluation
[0471] 1 g of the obtained cured product was cut and placed in a thermostatic chamber set at 100°C as a test piece. A dry nitrogen gas flow was allowed to flow for 24 hours. The weight of the test piece was then measured again. The rate of outgassing was calculated using the following formula, and outgassing resistance was evaluated using the following criteria. The lower the rate of outgassing, the higher the outgassing resistance.
[0472] Exhaust generation rate (%) = (weight after test - weight before test) / weight before test × 100%
[0473] ◎: The generation rate was less than 0.1%.
[0474] ○: The generation rate is 0.1% or more and less than 0.3%.
[0475] Δ: The generation rate is 0.3% or more and less than 1.0%.
[0476] ×: The generation rate is 1.0% or more.
[0477] Evaluation of resistance to yellowing under humidity and heat
[0478] After the obtained sealant cured product is allowed to stand for 24 hours in an atmosphere of temperature 23°C and relative humidity 50%, the transmission spectrum of the cured product is measured by a special machine for transmission color measurement (TZ-6000, manufactured by Nippon Denshoku Industries Co., Ltd.), and the initial b value is set. Then, the cured product is allowed to stand for 500 hours in a constant temperature and humidity machine set at 85°C and relative humidity 85%, and an accelerated test of resistance to wet heat yellowing is performed. The cured product after the test is also allowed to stand for 24 hours in an atmosphere of temperature 23°C and relative humidity 50%, and the transmission color is measured, and the b value after wet heat is set. The difference between the b value after wet heat and the initial b value is set as the change value Δb (Δb = b value after wet heat - initial b value). The resistance to wet heat yellowing of the cured product is evaluated by the following criteria.
[0479] ◎: Both the initial b value and the b value after wet heat treatment are 0.2 or less, and Δb is 0.1 or less.
[0480] ○: Either or both of the initial b value and the b value after wet heat treatment exceed 0.2, but are both 0.5 or less, and Δb is 0.2 or less.
[0481] Δ: Either or both of the initial b value and the b value after wet heat treatment exceed 0.5, but are both 1.0 or less, and Δb is 0.3 or less.
[0482] ×: Either or both of the initial b value and the b value after wet heat treatment exceeds 1.0, or Δb exceeds 0.3.
[0483] Thermal cycle resistance evaluation
[0484] The obtained sealant cured product was allowed to stand at -40°C for 30 minutes and then at 100°C for 30 minutes. This operation was repeated 100 times as one cycle. The state of the cured product was visually observed and the heat cycle resistance was evaluated according to the following criteria.
[0485] ◎: No change was observed at all.
[0486] ○: Bubbles are slightly observed, but cracks are not observed. Transparent.
[0487] Δ: A few bubbles or cracks are observed, and the image is slightly blurred.
[0488] ×: Bubbles or cracks are generated on the entire surface, and the surface is semi-transparent.
[0489] Corrosion resistance evaluation
[0490] After the above-mentioned wet heat yellowing resistance test, the surface of the copper foil was visually observed, and the corrosion resistance of the cured product was evaluated by dividing it into four levels.
[0491] ◎: No corrosion.
[0492] ○: Slightly corroded.
[0493] Δ: Slightly corroded.
[0494] ×: Significant corrosion.
[0495] [Table 9]
[0496]
[0497]
[0498] It is obvious from the results of Table 9 that the sealant composition of the embodiment contains a water-insoluble multifunctional (meth) acrylamide (A) and a polymerizable compound (B). Through the multiple isopropylidene groups and (meth) acrylamide groups of A, the obtained sealant cured product has high water resistance, less outgassing, and good resistance to wet heat yellowing, heat cycle resistance and corrosion resistance. In addition, due to the high mutual solubility of A and B, the transparency of the sealant cured product is also high. On the other hand, these physical properties of the cured product obtained by the curable composition of the comparative example are not satisfactory. The sealant composition disclosed in the present invention can be preferably used as a sealant for optical components, electrical equipment, etc.
[0499] Examples 63 to 67 and Comparative Examples 23 and 24 (Preparation and Evaluation of Curable Nail Cosmetics)
[0500] The active energy ray-curable composition obtained in Table 1, (meth)acrylamide (A), polymerizable compound (B), photopolymerization initiator (C) and other components were weighed in the mass ratio shown in Table 10, and mixed at 35° C. for one hour to prepare nail cosmetics of Examples and Comparative Examples. Using the obtained nail cosmetics, the curability and physical properties of the obtained cured films were evaluated by the following methods, and the results are shown in Table 10.
[0501] Evaluation of curing properties of nail cosmetics
[0502] The obtained curable nail cosmetic was applied to a nylon 6 test piece ("SHT-N6 (NC)" manufactured by Toray Plastic Seiko Co., Ltd.) using a bar coater (No. 12) in a film thickness of 10 μm, and then irradiated with ultraviolet light using a UV-LED lamp for gel nails (manufactured by BEAUTY NAILER, wavelength 405 nm, 48 W), and the time for the viscosity to disappear when the surface of the cured film is touched was measured. The curability of the nail cosmetic was evaluated according to the following criteria. The shorter the time required until the viscosity disappears, the higher the curability.
[0503] ◎: The stickiness disappears in less than 1 minute.
[0504] ○: The stickiness disappears in 1 minute or more and less than 3 minutes.
[0505] Δ: The stickiness disappears in 3 minutes or more and less than 10 minutes.
[0506] ×: The stickiness does not disappear even after 10 minutes or more.
[0507] Evaluation of the adhesion of nail cosmetics
[0508] The obtained curable nail cosmetic was applied to a nylon 6 test piece in the same manner as above, and a cured film was prepared by irradiating light for 3 minutes. The obtained cured film was used to make 100 1 mm square grids on the cured film using a cutter according to JIS K 5600, and after the adhesive tape was attached, the number of grids remaining on the test piece when peeled off at once was counted, and the adhesion of the nail cosmetic was evaluated according to the following criteria. The more the number of remaining grids, the higher the adhesion.
[0509] ◎: The number of remaining grids is 100.
[0510] ○: The number of remaining grids is 90 to 99.
[0511] Δ: The number of remaining grids is 60 to 89.
[0512] ×: The number of remaining squares is less than 60.
[0513] Evaluation of surface hardness of nail cosmetic cured film
[0514] The cured films of each example and comparative example were prepared in the same manner as in the evaluation of adhesion, and a pencil with a hardness of HB was used to apply a load of 750 g to the surface of the obtained film for painting, and the presence or absence of peeling and scratching was visually confirmed. The surface hardness of the nail cosmetic cured film was evaluated according to the following criteria. The less scratches or peeling occurred, the higher the surface hardness.
[0515] ○: Neither scratches nor peeling occurs. The surface hardness is HB or higher in pencil hardness.
[0516] Δ: No peeling occurred, but damage occurred.
[0517] ×: Peeling occurred.
[0518] Evaluation of surface gloss of cured film of nail cosmetics
[0519] The cured films of the respective Examples and Comparative Examples were prepared in the same manner as in the evaluation of adhesion, and the surface gloss of the cured films was visually observed and evaluated based on the following criteria.
[0520] ○: Glossy.
[0521] Δ: Reflection of light was confirmed, but blurriness was observed.
[0522] ×: No light reflection was observed, and the product was dull.
[0523] [Table 10]
[0524]
[0525]
[0526] It is clear from the results of Table 10 that in the performance evaluation using a commercially available UV lamp for gel nails, the curable nail cosmetics of the embodiments contain both (meth) acrylamide (A) and polymerizable compound (B), have excellent curability, and have high adhesion to nylon substrates (similarly, in nails with protein as the main component, materials with multiple amide groups). According to the results, the curable nail cosmetics of the present disclosure can be suitably used as gel nails for base gels directly applied to nails. In addition, the surface hardness and surface glossiness of the obtained cured film are both good, and it can also be suitably used as gel nails for top coating. On the other hand, the curable composition of the comparative example has low curability, and the surface hardness and surface glossiness of the cured film are low.
[0527] Examples 68 to 72 and Comparative Examples 25 and 26 (Preparation and Evaluation of Curable Dental Materials)
[0528] The curable composition, multifunctional (meth) acrylamide (A), polymerizable compound (B), photopolymerization initiator (C) and other components obtained in Table 1 were weighed according to the mass ratio shown in Table 11, and mixed at 35°C for one hour to prepare the curable dental materials of the embodiments and comparative examples. The solubility or dispersibility of the obtained curable dental materials was visually observed (in the case of mixing insoluble inorganic fillers). In addition, using the curable dental materials, dental material cured products were prepared by the following method, and the curability of the curable dental materials, the surface smoothness, hardness, and bonding strength of the obtained dental material cured products were evaluated. The evaluation results are shown in Table 11.
[0529] Evaluation of the solubility or dispersibility of curable dental materials
[0530] ⊚: The obtained composition was uniform and transparent.
[0531] ○: The obtained composition was uniform and translucent.
[0532] Δ: The obtained composition was cloudy and it was difficult to judge the uniformity.
[0533] ×: The obtained composition was not completely mixed.
[0534] Evaluation of the curability of curable dental materials
[0535] The obtained curable dental materials of the examples and comparative examples were filled with the composition in a polytetrafluoroethylene mold (20 mm × 20 mm × 10 mm) having a hole with a diameter of 6 mm in the center, and the mixture was crimped with a polypropylene film. A dental light irradiator (Tokuso Power Light, manufactured by Tokuyama Dental Co., Ltd., light output density 700 mW / cm 2 , light intensity on the irradiated surface 640mW / cm 2 Up to 650mW / cm 2 The light source is a halogen lamp with an irradiation diameter of 8 mm) and is placed in close contact with the polypropylene film for 30 seconds. The polypropylene film is peeled off and the cured product is touched by hand to confirm whether there is stickiness or uncured components. The curability is evaluated according to the following criteria.
[0536] ◎: Completely non-sticky (completely cured).
[0537] ○: Slightly sticky, but no fingerprints remain on the surface (almost completely cured, no need to wipe off the uncured components).
[0538] Δ: It is sticky and there are fingerprints on the surface (not completely cured, the uncured components must be wiped off).
[0539] ×: Severe stickiness, fingers sticking to the surface (large amount of uncured components remain, and cannot be used as a cured film).
[0540] Surface smoothness of cured dental materials
[0541] The surface of the cured product obtained in the above curability evaluation was visually observed to confirm smoothness and glossiness, and the surface smoothness was evaluated according to the following criteria.
[0542] ◎: The surface is smooth and glossy.
[0543] ○: The surface is generally smooth, but faint or slight irregularities are vaguely seen.
[0544] Δ: The entire surface is blurred, and some irregularities or grains are observed.
[0545] ×: The entire surface is blurred and covered with granular matter.
[0546] Hardness evaluation of cured dental materials
[0547] The cured product obtained in the curability evaluation of the curable dental material was polished and the Knoop hardness was measured using a microhardness tester manufactured by Matsuzawa Seiki (10 g, 20 seconds load, measurement temperature 23° C.). The higher the Knoop hardness, the higher the hardness of the cured dental material.
[0548] ◎: Knoop hardness is above 200KHN (equivalent to permanent tooth enamel).
[0549] ○: Knoop hardness is 70 KHN or more and less than 200 KHN (equivalent to dentine).
[0550] Δ: Knoop hardness does not reach 70KHN.
[0551] ×: Unable to measure because it was not cured.
[0552] Evaluation of bonding strength of cured dental materials (dentin bonding)
[0553] Grind the bovine mandibular front teeth with #1000 water-resistant abrasive paper under water injection, cut a flat dentin surface for bonding, spray compressed air for 10 seconds to dry it, attach a tape with a hole of 3 mm in diameter, and set the bonding surface. Then, a bonding test piece was made by a known method (refer to the method described in Japanese Patent Application Laid-Open No. 2010-208964). After the bonding test piece was immersed in 37°C water for 24 hours, the tensile bonding strength was measured using an Instron universal testing machine (crosshead speed 2 mm / min), which was set as the bonding strength between the enamel and dentin of the curable dental material obtained in the examples and comparative examples. In addition, the value of the tensile bonding strength is the average value of five test pieces.
[0554] ◎: The bonding strength between enamel and dentin is 20 MPa or more.
[0555] ○: Only one of the bonding strengths between enamel and dentin is 20 MPa or more.
[0556] Δ: The bonding strength between enamel and dentin is above 7 MPa.
[0557] ×: The bonding strength between enamel and dentin did not reach 7 MPa.
[0558] [Table 11]
[0559]
[0560] As can be clearly seen from the results in Table 11, the curable dental material of the embodiment contains (meth)acrylamide (A) and polymerizable compound (B) at the same time, has excellent solubility or dispersibility, and has high curability. In addition, the dental material cured product obtained in the embodiment has good hardness, surface smoothness and bonding strength. On the other hand, the curable dental material of the comparative example does not contain A and B at the same time, has low solubility or dispersibility, cannot be fully cured, and the hardness and surface smoothness of the obtained cured product are low, and the bonding strength is insufficient.
[0561] Examples 73 to 77 and Comparative Examples 27 and 28 (Preparation and Evaluation of Curable Decorative Coating Agents)
[0562] The curable composition obtained in Table 1, the multifunctional (meth)acrylamide (A), the polymerizable compound (B), the photopolymerization initiator (C) and other components were weighed according to the mass ratio shown in Table 12, and mixed at 35°C for one hour to prepare the curable decorative coating agents of the Examples and Comparative Examples. Using the obtained decorative coating agents, laminates were prepared by the following decorative processing, and the physical properties of the laminates were evaluated.
[0563] Fabrication of laminated bodies
[0564] The obtained decorative coating agent was applied to a PC film ("Panlite PC-2151" manufactured by Teijin Co., Ltd.) having a thickness of 180 μm using a bar coater (No. 6) so that the film thickness after drying was 5 μm. The film was then heated at 80° C. for three minutes and irradiated with ultraviolet light (the same variable flow conveyor device manufactured by EYE GRAPHICS as above, the same metal halide lamp as above, ultraviolet light intensity: 700 mW / cm 2 , integrated light quantity: 1000mJ / cm 2 ) to cure the coating film to obtain a laminate having a hard coating layer. The obtained laminate was cut and the surface tack resistance, surface hardness, scratch resistance of the hard coating layer of the laminate, and the elongation and bending resistance of the laminate were evaluated by the following methods. The results are shown in Table 12.
[0565] Evaluation of the anti-sticking property of the hard coating layer of the laminate
[0566] The obtained laminate was used, and the surface of the hard coat layer was touched with a finger to evaluate the stickiness.
[0567] ◎: No stickiness at all.
[0568] ○: Slightly sticky, but no fingerprints remain on the surface.
[0569] Δ: It is sticky and there are fingerprints left on the surface.
[0570] ×: Very sticky, fingers stick to the surface.
[0571] Evaluation of elongation of laminated body
[0572] The obtained laminate was cut into pieces of 50 mm in length and 15 mm in width, fixed to a Tensilon universal testing machine RTA-100 (manufactured by Orientec) with a chuck distance of 25 mm, and stretched in one direction at a speed of 250 mm / min in an oven set at a temperature of 150°C while visually observing the appearance, and the length (mm) of the test piece when the coating was cracked or turned white was measured. The elongation was calculated by the following method and evaluated by the following criteria.
[0573] Elongation (%) = (length of test specimen after test / 25) × 100%
[0574] ◎: The elongation is 200% or more.
[0575] ○: The elongation is 150% or more and less than 200%.
[0576] Δ: The elongation is 110% or more and less than 150%.
[0577] ×: The elongation is less than 110%.
[0578] Evaluation of surface hardness of hard coating layer of laminate
[0579] The hard coating layer of the laminate was scratched with a pencil at an angle of 45° for about 10 mm in accordance with JIS K 5600. The hardest pencil with no scratches on the surface of the laminate was taken as the pencil hardness, and the surface hardness was evaluated according to the following criteria.
[0580] ◎: Pencil hardness is 2H or more.
[0581] ○: Pencil hardness is HB to H.
[0582] Δ: Pencil hardness is 3B to B.
[0583] ×: Pencil hardness is 4B or less.
[0584] Evaluation of scratch resistance of hard coating layer of laminate
[0585] #0000 steel wool was passed back and forth 10 times on the hard coating layer of the laminate with a load of 200 g, and the surface of the hard coating layer was visually observed. The scratch resistance was evaluated according to the following criteria.
[0586] ⊚: No peeling or damage of the film was observed.
[0587] ○: Slightly fine damage was observed in a part of the film.
[0588] Δ: Striated damage was observed throughout the film.
[0589] ×: Film peeling occurred.
[0590] Evaluation of bending resistance of laminated bodies
[0591] The test piece of the laminate was bent 180° with the hard coating surface facing outward, a weight of 1 kg was placed thereon and left for 10 minutes, the surface of the laminate was visually observed for cracks, and the bending resistance was evaluated according to the following criteria.
[0592] ◎: No cracks were observed at all.
[0593] ○: The bent portion was partially whitened.
[0594] Δ: Partial cracking is observed at the bent portion.
[0595] ×: Cracks were observed at the bent portion.
[0596] [Table 12]
[0597]
[0598] It is obvious from the results of Table 12 that the curable decorative coating agent of the embodiment contains multifunctional (meth) acrylamide (A) and a polymerizable compound (B), which is applied to the surface of a general plastic substrate and cured, thereby easily obtaining a laminate having a decorative coating layer (decorative coating film). The surface of the obtained laminate (coated surface such as a hard coating) is resistant to sticking, has high hardness and scratch resistance, and the obtained laminate has good bending resistance. On the other hand, the curable decorative coating agent of the comparative example did not confirm the same decorative performance. The decorative coating agent disclosed in the present invention can be suitably used for a variety of decorative forming, decorative processing, and decorative printing such as decorative films, decorative sheets, and decorative coatings.
[0599] This disclosure contains the following contents.
[0600] (1) A curable composition comprising a water-insoluble polyfunctional (meth)acrylamide (A) and a polymerizable compound (B) other than (A).
[0601] (2) The curable composition as described in (1) above, wherein the solubility parameter (SP value) of the polyfunctional (meth)acrylamide (A) is 8.8 (cal / cm 3 ) 1 / 2 To 11.0 (cal / cm 3 ) 1 / 2 .
[0602] (3) The curable composition as described in (1) or (2) above, wherein the solubility parameter (SP value) of the polymerizable compound (B) is 8.5 (cal / cm 3 ) 1 / 2 To 14.5 (cal / cm 3 ) 1 / 2 .
[0603] (4) The curable composition according to any one of (1) to (3) above, wherein the absolute value of the difference between the solubility parameter (SP value) of the polyfunctional (meth)acrylamide (A) and the solubility parameter (SP value) of the polymerizable compound (B) is 3.0 (cal / cm 3 ) 1 / 2 the following.
[0604] (5) The curable composition according to any one of (1) to (4) above, wherein the polyfunctional (meth)acrylamide (A) has an acrylic acid equivalent of 180 or more.
[0605] (6) The curable composition according to any one of (1) to (5) above, wherein the polyfunctional (meth)acrylamide (A) is a compound represented by the general formula [1] to [4].
[0606] [Chemical formula 1]
[0607]
[0608] [Chemical formula 2]
[0609]
[0610] [Chemical formula 3]
[0611]
[0612] [Chemical formula 4]
[0613]
[0614] (In formula [1] to formula [4], R 1 represents a hydrogen atom or a methyl group, and may be the same or different. 2 and R 3 All represent a divalent chain hydrocarbon group having 3 carbon atoms, and may be a linear or branched structure, and may be the same or different. 4 represents a hydrogen atom or a chain hydrocarbon group having 1 to 2 carbon atoms. n is an integer from 1 to 70, x1 and z1 are each independently an integer from 1 to 10, y1 is an integer from 1 to 40, x2, y2 and z2 are each independently an integer from 1 to 30, s3, x3, y3 and z3 are each independently an integer from 1 to 20, and m is an integer of 0 or 1.
[0615] (7) The curable composition as described in any one of (1) to (6) above, wherein the content of the polyfunctional (meth)acrylamide (A) is 1% to 95% by mass, and the content of the polymerizable compound (B) is 5% to 99% by mass, relative to the total mass of the curable composition.
[0616] (8) A curable composition as described in any one of (1) to (7) above, wherein the polymerizable compound (B) has in the molecule one or more polymerizable groups selected from the group consisting of a (meth)acrylate group, a (meth)acrylamide group, a vinyl group, a vinyl ether group, a methyl vinyl ether group, an allyl group, a (meth)allyl ether group, a maleimide group, an α-substituted maleimide group, and an α,β-substituted maleimide group.
[0617] (9) A curable composition as described in any one of (1) to (8) above, wherein the polymerizable compound (B) contains a monofunctional polymerizable compound (b1) and / or a polyfunctional polymerizable compound (b2), and the content of (b1) is 5% to 80% by mass, and the content of (b2) is 0% to 40% by mass, relative to the total mass of the curable composition.
[0618] (10) The curable composition according to any one of (1) to (9) above, further comprising a polymerizable polymerization initiator (C) (excluding (A) and (B)), wherein the content of (C) is 0.1% by mass to 20% by mass relative to the total mass of the curable composition.
[0619] (11) The curable composition according to any one of (1) to (10) above, comprising a quaternary salt monomer as the polymerizable compound (B), wherein the content of the quaternary salt monomer is 0.1% by mass to 30% by mass based on the total mass of the curable composition.
[0620] (12) A coating composition comprising the curable composition according to any one of (1) to (11) above.
[0621] (13) An adhesive composition comprising the curable composition according to any one of (1) to (11) above.
[0622] (14) An adhesive composition comprising the curable composition according to any one of (1) to (11) above.
[0623] (15) An ink composition comprising the curable composition according to any one of (1) to (11) above.
[0624] (16) An aqueous ink composition comprising the curable composition according to any one of (1) to (11) above.
[0625] (17) An ink composition for three-dimensional modeling, comprising the curable composition described in any one of (1) to (11) above.
[0626] (18) An aqueous coating composition comprising the curable composition according to any one of (1) to (11) above.
[0627] (19) A sealant composition comprising the curable composition according to any one of (1) to (11) above.
[0628] (20) A nail cosmetic comprising the curable composition according to any one of (1) to (11) above.
[0629] (21) A dental material comprising the curable composition according to any one of (1) to (11) above.
[0630] (22) A decorative coating agent comprising the curable composition according to any one of (1) to (11) above.
[0631] [Industrial Applicability]
[0632] As described above, the curable composition of the present invention contains a multifunctional (meth)acrylamide (A) and a polymerizable compound (B), wherein (A) is amphiphilic and can be mixed with a variety of (B) in a wide range of proportions. In addition, as required, a polymerizable polymerization initiator, a polymerizable compound, a non-polymerizable component, and an additive other than (A) and (B) may be contained, and as a result, the curable composition can be preferably used for applications ranging from general products to various special coatings, adhesives, bonding agents, inks, water-based inks, three-dimensional modeling inks, water-based coatings, sealants, nail cosmetics, dental materials, decorative coatings, and the like.
Claims
1. A curable composition comprising a water-insoluble polyfunctional (meth)acrylamide (A) and a polymerizable compound (B) other than (A).
2. The curable composition according to claim 1, wherein the solubility parameter (SP value) of the multifunctional (meth)acrylamide (A) is 8.8 (cal / cm 3 ) 1 / 2 to 11.0(cal / cm 3 ) 1 / 2 The solubility parameter (SP value) of the polymerizable compound (B) is 8.5 (cal / cm 3 ) 1 / 2 To 14.5 (cal / cm 3 ) 1 / 2 , the absolute value of the difference between the SP values of A and B is less than 3.
0.
3. The curable composition according to claim 1 or 2, wherein the polyfunctional (meth)acrylamide (A) is a compound represented by the general formula [1] to the general formula [4]; [Chemical formula 1] [Chemical formula 2] [Chemical formula 3] [Chemical formula 4] In formula [1] to formula [4], R 1 represents a hydrogen atom or a methyl group, which may be the same or different; R 2 and R 3 All represent a divalent chain hydrocarbon group having 3 carbon atoms, which may be a straight chain or a branched chain structure, and may be the same or different; R 4 represents a hydrogen atom or a chain hydrocarbon group having 1 to 2 carbon atoms; n is an integer from 1 to 70, x1 and z1 are each independently an integer from 1 to 10, y1 is an integer from 1 to 40, x2, y2 and z2 are each independently an integer from 1 to 30, s3, x3, y3 and z3 are each independently an integer from 1 to 20, and m is an integer of 0 or 1.
4. The curable composition according to any one of claims 1 to 3, wherein the content of the polyfunctional (meth)acrylamide (A) is 1% to 95% by mass, and the content of the polymerizable compound (B) is 5% to 99% by mass, relative to the total mass of the curable composition. 5 . A coating composition comprising the curable composition according to claim 1 . 6 . An adhesive composition comprising the curable composition according to claim 1 .
7. An adhesive composition comprising the curable composition according to any one of claims 1 to 4.
8. An ink composition comprising the curable composition according to any one of claims 1 to 4. 9 . An aqueous ink composition comprising the curable composition according to claim 1 . 10 . An ink composition for three-dimensional modeling, comprising the curable composition according to claim 1 .
11. An aqueous coating composition comprising the curable composition according to any one of claims 1 to 4. 12 . A sealant composition comprising the curable composition according to claim 1 .
13. A nail cosmetic comprising the curable composition according to any one of claims 1 to 4.
14. A dental material comprising the curable composition according to any one of claims 1 to 4.
15. A decorative coating agent comprising the curable composition according to any one of claims 1 to 4.
